Heterogeneous bimetallic catalyst, preparation method and application thereof
By using the heterogeneous bimetallic catalyst CoCu/ZrO2, the problems of high efficiency, environmental protection and recyclability in the preparation of ethylene glycol from oxalate were solved, and high selectivity and high yield of ethylene glycol were achieved, which is suitable for industrial continuous flow method.
Patent Information
- Application Number
- CN202380093855.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-13
- Filing Date
- 2023-12-13
- Publication Date
- 2025-09-23
AI Technical Summary
Existing technologies make it difficult to prepare ethylene glycol from oxalate in an efficient, low-cost and environmentally friendly manner, and traditional catalysts have problems such as the use of environmentally harmful substances and the difficulty in recovering the catalysts.
A heterogeneous bimetallic catalyst CoCu/support, especially CoCu/ZrO2, is used to prepare ethylene glycol through the hydrogenation reaction of oxalate. The catalyst is prepared using a non-toxic green solvent, and copper and cobalt are fixed on the support. The catalyst can be recovered and reused.
The method achieves high selectivity and high yield conversion of oxalate to ethylene glycol, the catalyst is easy to recover, environmental pollution is reduced, and the method is suitable for industrial continuous flow method.
Smart Images

Figure BDA0005543379380000011 
Figure BDA0005543379380000012 
Figure BDA0005543379380000081
Abstract
Description
Technical Field
[0001] The present invention relates to a novel heterogeneous bimetallic catalyst, a method for preparing the same and its use, in particular for the synthesis of ethylene glycol from the hydrogenation of oxalic acid esters. Background Art
[0002] Ethylene glycol is an important raw material in the chemical industry and can be used in a variety of applications, such as antifreeze or refrigerants, in particular in the production of textile fibers and polyester resins. Ethylene glycol can be used as a monomer in the manufacture of polyesters, and in particular in the manufacture of PET (polyethylene terephthalate) in the presence of terephthalic acid. PET is a polymer widely used in the textile industry, which is currently produced mainly from petroleum-based products that generate large amounts of greenhouse gases (including carbon dioxide).
[0003] The typical process for making ethylene glycol is carried out from naphtha and is as follows:
[0004]
[0005] Scheme 1: Classical method for producing ethylene glycol
[0006] Carbon dioxide (CO2) recovery is a major challenge in reducing greenhouse gas emissions. Another pathway for ethylene glycol synthesis is the hydrogenation of oxalic acid esters or oxalamides. Oxalic acid esters are high-value-added raw materials in the chemical industry. They are used on a large scale in the production of various dyes, pharmaceuticals, solvents, extractants, and various intermediates in the fine chemical industry.
[0007] Thus, CO2 consumption can be achieved during the synthesis of oxalate esters, which are precursors for the production of ethylene glycol by transition metal (as homogeneous or heterogeneous catalyst) catalyzed hydrogenation, as illustrated below:
[0008]
[0009] Scheme: Preparation of ethylene glycol from CO2
[0010] Homogeneous transition metal-based catalysts are catalysts that are soluble in the reaction solvent and form a single phase.
[0011] Heterogeneous transition metal-based catalysts are insoluble catalysts that participate in reactions involving two phases (eg, liquid and solid).
[0012] Supported bimetallic catalysts consist of a support on the surface of which particles of the two metals are dispersed and fixed in the form of the oxides of these metals, or in reduced form, or even as a mixture of these two forms.
[0013] The support is advantageously an oxide, for example alumina or silica.
[0014] It is understood that a bimetallic catalyst of two metals (Metal-1 and Metal-2) comprises two metal species (Metal-1 and Metal-2) on a support on a surface thereof accessible to a substrate for catalytic reaction.
[0015] Thus, a monometallic supported catalyst consists of a support on which particles of a single metal are dispersed and fixed in oxidic form, or in reduced form, or even in a mixture of both forms.
[0016] Typically, the hydrogenation reaction from oxalate to ethylene glycol is catalyzed by a catalyst comprising a metal. For example, the hydrogenation step is carried out using a copper-based catalyst.
[0017] In an article by Yuxi Xu et al. (Catal. Sci. Technol., 2022, 12 6782), the use of a copper monometallic catalyst supported on zirconium dioxide, Cu / ZrO2, for the hydrogenation of oxalate to ethylene glycol is described. The authors investigated the influence of the crystalline phase of the substrate synthesized at different temperatures and correlated the catalyst structure with the catalytic performance.
[0018] In an article by Kong et al. (Catalysis Communications, 65, 2015, 46-50), the use of a cobalt-based catalyst, CoCu / ZnO, supported on zinc oxide, for oxalate hydrogenation in the presence of copper as a promoter is described. The monometallic Co / ZnO catalyst for oxalate hydrogenolysis exhibits selectivity for methane formation (80%) over ethylene glycol formation. The presence of copper as a promoter enables the direct, selective formation of ethylene glycol.
[0019] For many years, there has been a need for a low-cost, environmentally friendly route to the production of ethylene glycol.
[0020] To date, a search has been underway for heterogeneous catalysts that are easy to prepare, allow for the efficient and environmentally friendly synthesis of ethylene glycol from oxalates, are easily industrializable and safe.
[0021] Ethylene glycol is also a model compound for the cleavage of C-C and / or C-O bonds of diol groups -CHOH-CHOH- present in carbohydrate molecules (polyols) contained in biomass by the action of hydrogen (i.e., hydrogenolysis). Therefore, a catalyst capable of cleaving C-C and C-O bonds of ethylene glycol by hydrogenolysis will be able to depolymerize biomass by cleaving C-C and / or C-O bonds of diol groups present in biomass. Summary of the Invention
[0022] One of the objects of the present invention is to propose a process for preparing ethylene glycol from oxalic esters by reaction using heterogeneous bimetallic catalysts, in particular based on copper and cobalt.
[0023] Another object of the present invention is a process for preparing ethylene glycol with high efficiency and selectivity.
[0024] Another object of the present invention is to prepare ethylene glycol without using toxic reagents.
[0025] Another object of the present invention is to prepare ethylene glycol using recoverable or recycled reagents and efficient and reusable heterogeneous catalysts.
[0026] Another object of the present invention is to provide a process for hydrogenolysis of ethylene glycol using a heterogeneous bimetallic catalyst.
[0027] Another object of the present invention is to provide a process for depolymerization of biomass using a heterogeneous bimetallic catalyst.
[0028] Another object of the present invention is to provide novel supported heterogeneous bimetallic catalysts.
[0029] It is another object of the present invention to provide heterogeneous catalysts that can be used in continuous flow processes.
[0030] Another object of the present invention is to provide a simple, industrial and optimized process for preparing this catalyst. DETAILED DESCRIPTION
[0031] use
[0032] A first object of the present invention is the use of a supported bimetallic catalyst having the formula CoCu / support in the implementation of a process for preparing ethylene glycol from oxalate compounds, wherein the oxalate compounds are hydrogenated by hydrogen (H2) to obtain ethylene glycol, the catalyst comprising cobalt and copper on a support.
[0033] In the present invention, the terms "hydrogen" and "dihydro" define the same H2 molecule.
[0034] It is understood that the catalyst CoCu / support is a heterogeneous catalyst, wherein the catalyst is in a solid phase and the reactants are in a liquid or gaseous state.
[0035] The advantage of using a heterogeneous catalyst is that it facilitates the separation of the catalyst from other species participating in the reaction, allows for easy recovery and reuse of the catalyst, and limits contamination of the product with transition metals.
[0036] The use of heterogeneous catalysts also has the advantage that, when operating under continuous flow, the catalyst can be immobilized in the reactor within an enclosure (eg a jacket) and a catalyst-free product can thus be obtained at the reactor outlet.
[0037] For the purposes of this invention, "catalyst" or "supported catalyst" refers to a material composed of a support on which the catalytic sites are located. It will be understood that the bimetallic cobalt and copper catalyst includes the support as well as atoms of the cobalt and copper elements. The total weight of the catalyst is equivalent to the weight of the support plus the weight of the cobalt and copper elements.
[0038] According to a specific embodiment, the present invention relates to the use of a supported bimetallic catalyst CoCu / support in implementing a method for preparing ethylene glycol from an oxalate compound, wherein the oxalate compound is hydrogenated by hydrogen (H2) to obtain ethylene glycol. The catalyst comprises copper and cobalt on a support, wherein the support is selected from zirconium dioxide (ZrO2), silicon dioxide (SiO2) or aluminum oxide (Al2O3), in particular zirconium dioxide (ZrO2).
[0039] Using catalyst CoCu / ZrO2
[0040] According to a specific embodiment, the present invention relates to the use of a supported bimetallic catalyst having the formula CoCu / ZrO2 in implementing a method for preparing ethylene glycol from oxalate compounds, wherein the oxalate compounds are hydrogenated by hydrogen (H2) to obtain ethylene glycol, wherein the catalyst comprises cobalt and copper on a zirconium dioxide support.
[0041] The present inventors have unexpectedly observed a synergistic effect between copper and cobalt in a heterogeneously supported bimetallic catalyst that significantly increases the yield and selectivity of oxalate hydrogenation to ethylene glycol. While monometallic cobalt catalysts on zirconium dioxide are inactive for oxalate hydrogenation to ethylene glycol, experiments (see Examples 21 and 22) demonstrate that cobalt in the CuCo / ZrO catalyst functions as a promoter, boosting the yield and selectivity of ethylene glycol.
[0042] In fact, they found that the yield using a monometallic copper catalyst was about 12% and the selectivity was 13%, while the monometallic cobalt-based catalyst was inactive. According to the present invention, the use of a bimetallic cobalt and copper catalyst on an oxide support made it possible to achieve a yield of 84% and a selectivity of 95%.
[0043] The present inventors have also observed that zirconium dioxide ZrO2 supports achieve better results compared to other oxide supports such as silicon dioxide (SiO2), ceria (CeO2) or alumina (γ-Al2O3).
[0044] According to a specific embodiment, the present invention relates to the use of a supported bimetallic catalyst having the formula CoCu / ZrO2 in implementing a method for preparing ethylene glycol from oxalate compounds, wherein the oxalate compounds are hydrogenated by hydrogen (H2) to obtain ethylene glycol, and the catalyst comprises cobalt and copper on a zirconium dioxide support.
[0045] According to a specific embodiment, the present invention relates to the use as defined above, wherein the oxalate is selected from dimethyl oxalate, diethyl oxalate, dibenzyl oxalate, di-tert-butyl oxalate, diisopropyl oxalate, diphenyl oxalate, in particular selected from dimethyl oxalate or diethyl oxalate, preferably diethyl oxalate.
[0046] Advantageously, the oxalic acid esters used are obtainable by carbonylation of alcohols in the presence of CO and oxygen.
[0047] Advantageously, the carbon monoxide CO used for preparing the oxalate ester is produced by electrolysis of carbon dioxide CO2 to carbon monoxide CO.
[0048] Therefore, the synthesis of ethylene glycol is advantageously carried out from the recovery of CO2 and alcohol.
[0049] Use of catalyst preparation via soft chemistry
[0050] According to a particular embodiment, the invention relates to the use as defined above, wherein the catalyst is prepared by mixing the support in powder form with an aqueous solution of copper and cobalt salts, followed by drying and calcination.
[0051] According to a particular embodiment, the invention relates to the use as defined above, wherein the catalyst is prepared by mixing the support in powder form with an aqueous solution of copper and cobalt salts without additives or surfactants, in particular without ammonia solution, and then drying and calcining the material obtained.
[0052] It will be appreciated that the mixture of the support in powder form with the aqueous solution of copper and cobalt salts consists in contacting the solution of cobalt and copper salts with the support and thereby impregnating the support with the cobalt and copper salts, i.e. depositing cobalt and copper atoms on the surface of the support.
[0053] "Drying" refers to an operation consisting of heating the material in ambient air at a temperature of about 60°C to 100°C for a period of 10 to 24 hours in a closed enclosure to dry the material, i.e., to remove water molecules (i.e., free water, water adsorbed on the surface or in the interstitial space).
[0054] "Calcination" refers to an operation consisting of heating a solid material in ambient air in a closed enclosure at elevated temperatures of about 400°C to 1000°C to activate it or change the physical properties of the support and to remove bound water and salts of metal precursors (e.g., nitrates and acetates). After calcination, the material is free of water.
[0055] Advantageously, the catalyst used is prepared by the following preparation method, which comprises the following steps:
[0056] Step A: Dissolve in an aqueous solution (5 mL to 10 mL by volume of water)
[0057] The cobalt salt and copper salt are impregnated on a zirconium dioxide support in powder form, with the ratio of the mass of the solution to the mass of the support being 0.6 to 1.0;
[0058] To obtain the catalyst CoCu / ZrO2 in the form of a homogeneous mixture,
[0059] Step B: drying the homogeneous mixture to obtain the catalyst CoCu / ZrO2 in the form of a dry homogeneous mixture,
[0060] • Activation step C: comprises calcining the dried homogeneous mixture to obtain the catalyst.
[0061] For the purposes of the present invention, a "homogeneous mixture" means a homogeneous material obtained by mixing an aqueous solution of a metal salt, which is uniformly distributed on the surface of the particles constituting the support and in the interstices of said particles, with a support in solid powder form.
[0062] A "dried homogeneous mixture" is a homogeneous mixture from which most of the free water molecules adsorbed on the surface of the particles of the support or in the interstices have been removed, for example, by drying at 60° C. to 100° C. (particularly at 80° C.) to obtain a powder. The preparation of the catalyst results in the formation of the corresponding insoluble metal oxides, since the metal salts (e.g., nitrates) of the metals are completely removed after the calcination step at 600° C.
[0063] Advantageously, during the impregnation of step A, the aqueous solution containing the cobalt and copper salts is free of additives and surfactants. In other words, the aqueous impregnation solution consists of a demineralized aqueous solution in which the cobalt and copper salts are dissolved.
[0064] Advantageously, the cobalt salt is cobalt nitrate and the copper salt is copper nitrate.
[0065] Therefore, the use according to the present invention is carried out by preparing the catalyst using an aqueous solution, which is a non-hazardous green solvent compared to the organic solvents used in the prior art. Advantageously, no additional additives and surfactants are required in the synthesis of the catalyst, making it more industrializable at a lower cost.
[0066] "Green solvents" are non-toxic, biodegradable or agro-based alternative solvents that have the same properties as the toxic solvents they replace.
[0067] Use of catalysts with properties related to specific surface area
[0068] According to a particular embodiment, the present invention relates to the use as defined above, wherein the catalyst has a surface area of 1 m 2 / g to 250m 2 / g.
[0069] 1m 2 / g to 250m 2 The range of / g includes the following ranges: 1m 2 / g to 25m 2 / g; 25m 2 / g to 50m 2 / g; 50m 2 / g to 75m 2 / g;75m 2 / g to 100m 2 / g; 100m 2 / g to 125m 2 / g; 125m 2 / g to 150m 2 / g; 150m 2 / g to 175m 2 / g; 175m 2 / g to 200m 2 / g; 200m 2 / g to 225m 2 / g; 225m 2 / g to 250m 2 / g.
[0070] According to a particular embodiment, the present invention relates to the use as defined above, wherein the catalyst has a surface area of 1 m 2 / g to 50m 2 / g.
[0071] 1m 2 / g to 50m 2 The range of / g includes the following ranges: 1m 2 / g to 10m2 / g; 10m 2 / g to 20m 2 / g; 20m 2 / g to 30m 2 / g; 30m 2 / g to 40m 2 / g; 40m 2 / g to 50m 2 / g.
[0072] According to a particular embodiment, the present invention relates to the use as defined above, wherein the catalyst has a surface area of 1 m 2 / g to 10m 2 / g, preferably about 5m 2 / g.
[0073] 1m 2 / g to 10m 2 The range of / g includes the following ranges: 1m 2 / g to 2m 2 / g; 2m 2 / g to 3m 2 / g; 3m 2 / g to 4m 2 / g; 4m 2 / g to 5m 2 / g; 5m 2 / g to 6m 2 / g; 6m 2 / g to 7m 2 / g;7m 2 / g to 8m 2 / g;8m 2 / g to 9m 2 / g、9m 2 / g to 10m 2 / g, especially about 5m 2 / g.
[0074] The present inventors unexpectedly found that the BET analysis of the 2 / g specific surface area of ZrO2 support, with the same cobalt and copper content of the catalyst CoCu / ZrO2, the use of 5m 2 / g to 7m 2 / g specific surface area of ZrO2 carrier prepared with 1m 2 / g to 50m 2 / g, especially 1m 2 / g to 10m 2 / g of low specific surface area CoCu / ZrO2 bimetallic catalyst, allowing for improved yield and selectivity of the hydrogenation reaction of oxalate to ethylene glycol. Thus, unexpectedly, in terms of yield and selectivity of the hydrogenation reaction of oxalate to ethylene glycol, a catalyst with a surface area of about 5m 2 / g of low specific surface area catalysts are more than 50m 2 Catalysts with a surface area of 1.5-2.5 cm / g are more efficient. It is expected that catalysts with a larger surface area will be more advantageous in catalysis because it facilitates exchange.
[0075] Using catalysts with specific crystal structures
[0076] According to a particular embodiment, the invention relates to the use as defined above, wherein said catalyst comprises a crystalline phase, crystallized in the monoclinic system as analyzed by X-ray diffraction.
[0077] "Monoclinic" refers to a crystal system having one of the following symmetry point groups: 2, m, or 2 / m.
[0078] According to a particular embodiment, the invention relates to the use as defined above, wherein said crystalline phase represents from 50% to 90% of the total weight of the catalyst.
[0079] According to a particular embodiment, the invention relates to the use as defined above, wherein the crystalline phase is baddeleyite.
[0080] According to a particular embodiment, the invention relates to the use as defined above, wherein the catalyst support is natural zirconium dioxide (ZrO2) crystallized as monoclinic zirconite.
[0081] For the purposes of the present invention, "badgeonis" refers to natural zirconium oxide having the formula ZrO2, containing 0.1% to 5% hafnium oxide, and crystallizing in the monoclinic system. The characteristics of baddeleyite (e.g., its composition and crystal structure, particularly its space group and lattice dimensions) are reported and provided in the prior art and are known to those skilled in the art, for example, by Kudoh, Y. et al. (Phys Chem Minerals 13, 233-237 (1986)) or McCullough, J. D. et al. (Acta Crystallographica 12 (1959) 507-511).
[0082] According to a particular embodiment, the invention relates to the use as defined above, wherein the catalyst support made of zirconium dioxide ZrO2 comprises impurities such as hafnium (Hf), rhenium (Re) and silicon (Si) atoms.
[0083] Advantageously, the mass ratio between hafnium atoms and zirconium atoms (Hf / Zr) is less than 5%.
[0084] Advantageously, the mass ratio between rhenium atoms and zirconium atoms (Re / Zr) is less than 5%.
[0085] Advantageously, the mass ratio between silicon atoms and zirconium atoms (Si / Zr) is less than 2%.
[0086] According to a particular embodiment, the invention relates to the use as defined above, wherein the catalyst has a microstructure whose crystallite size is between 15 nm and 100 nm, preferably between 15 nm and 50 nm.
[0087] The crystal structure of the catalyst can be analyzed by powder X-ray diffraction. By comparing the diffraction peaks in the obtained diffraction pattern with reference materials, the phases present and their structures can be analyzed.
[0088] For example, the baddeleyite crystalline phase of zirconium dioxide ZrO 2 is shown in ICDD reference no. 00-037-1484.
[0089] From the diffraction pattern, the grain size can be estimated according to the following Scherrer formula:
[0090]
[0091] The range of "15 nm to 100 nm" includes the following ranges: 15 nm to 20 nm; 20 nm to 30 nm; 30 nm to 40 nm; 40 nm to 50 nm; 50 nm to 60 nm; 60 nm to 70 nm; 70 nm to 80 nm; 80 nm to 90 nm; 90 nm to 100 nm.
[0092] According to a particular embodiment, the present invention relates to the use as defined above, wherein:
[0093] The catalyst has a surface area of 1 m 2 / g to 250
[0094] m 2 / g, especially 1m 2 / g to 50m 2 / g,
[0095] - The catalyst comprises a crystalline phase, which is crystallized in a monoclinic system according to X-ray diffraction analysis.
[0096] According to a particular embodiment, the present invention relates to the use as defined above, wherein:
[0097] The catalyst has a surface area of 1 m 2 / g to 10
[0098] m 2 / g,
[0099] - the catalyst comprises a crystalline phase, which, as determined by X-ray diffraction analysis, is a monoclinic zircon crystal, the size of which is preferably between 15 nm and 100 nm, and
[0100] - optionally including impurities such as hafnium (Hf), rhenium (Re) and silicon (Si) atoms.
[0101] According to a particular embodiment, the present invention relates to the use as defined above, wherein the catalyst has a surface area of 1 m 2 / g to 250m 2 / g, especially 1m 2 / g to 50m 2 / g, preferably, 1m 2 / g to 10m 2 / g, especially about 5m 2 / g,
[0102] Optionally, the catalyst includes a crystalline phase, which is monoclinic crystallized by X-ray diffraction analysis, and in particular, the crystalline phase accounts for 50% to 90% of the total weight of the catalyst. Preferably, the crystalline phase is baddeleyite, and its grain size is preferably 15nm to 100nm.
[0103] Using catalysts with specific Cu and Co contents
[0104] According to a particular embodiment, the invention relates to the use as defined above, wherein the total content of the bimetallic elements copper and cobalt is between 0.5% and 25% by weight of the total catalyst.
[0105] The total weight of the catalyst includes the mass of the support and the mass of the cobalt and copper bimetallic elements.
[0106] The range of 0.5% to 25% includes the following ranges: 0.5% to 5%; 5% to 10%; 10% to 15%; 15% to 20%; 20% to 25%.
[0107] According to a particular embodiment, the invention relates to the use as defined above, wherein the total content of the bimetallic elements copper and cobalt is between 5% and 20% by weight of the total catalyst.
[0108] The "total content of bimetallic elements copper and cobalt" refers to the content of elemental copper and cobalt added to the catalyst.
[0109] According to a particular embodiment, the invention relates to the use as defined above, wherein the total content of elemental copper is from 1% to 25% by weight of the total catalyst, in particular from 1% to 10% by weight of the total catalyst.
[0110] According to a particular embodiment, the invention relates to the use as defined above, wherein the total content of elemental cobalt is between 1% and 25% by weight of the total catalyst, in particular between 1% and 10% by weight of the total catalyst.
[0111] According to a particular embodiment, the present invention relates to the use as defined above, wherein:
[0112] - a total content of elemental copper of 1 to 25% by weight, based on the total weight of the catalyst, in particular of 1 to 10% by weight, based on the total weight of the catalyst,
[0113] - and the total content of cobalt element is 1% to 25% based on the total weight of the catalyst,
[0114] In particular, it is from 1 to 10% by weight, based on the total weight of the catalyst.
[0115] According to a particular embodiment, the invention relates to the use as defined above, wherein the mass of copper is greater than the mass of cobalt.
[0116] According to a particular embodiment, the invention relates to the use as defined above, wherein the mass of cobalt is greater than the mass of copper.
[0117] According to a particular embodiment, the invention relates to the use as defined above, wherein the weight ratio of copper to cobalt varies from 1:1 to 1:10, in particular from 1:1 to 1:5.
[0118] According to a particular embodiment, the invention relates to the use as defined above, wherein the mass composition of cobalt and copper of the catalyst is chosen from Co(10%)Cu(5%) and Co(15%)Cu(5%).
[0119] According to a particular embodiment, the invention relates to the use as defined above, wherein the weight ratio of cobalt to copper varies from 1:1 to 1:10.
[0120] According to a particular embodiment, the invention relates to the use as defined above, wherein the weight ratio of cobalt to copper varies from 1:1 to 1:5.
[0121] According to a particular embodiment, the present invention relates to the use as defined above, wherein:
[0122] - the weight ratio of cobalt to copper varies from 1:1 to 1:5,
[0123] - a copper content of 10% based on the total weight of the catalyst,
[0124] - and a cobalt content greater than or equal to 2% by weight of the total catalyst.
[0125] According to a particular embodiment, the present invention relates to the use as defined above, wherein
[0126] - the weight ratio of cobalt to copper ranges from 1:2 to 1:5,
[0127] - a copper content of 10% based on the total weight of the catalyst,
[0128] - and a cobalt content greater than or equal to 2% by weight of the total catalyst.
[0129] According to a particular embodiment, the present invention relates to the use as defined above, wherein:
[0130] - the weight ratio of cobalt to copper varies from 1:2 to 1:5,
[0131] - a copper content of 10% based on the total weight of the catalyst,
[0132] - and a cobalt content greater than or equal to 2% by weight of the total catalyst,
[0133] - and a specific surface area of 1 m2 measured by BET 2 / g to 10m 2 / g.
[0134] The inventors have unexpectedly observed that when the catalyst CoCu / ZrO2 comprises a mass of copper greater than the mass of cobalt, in particular when the weight ratio of cobalt to copper varies from 1:1 to 1:5, and when the copper content is 10% by weight, relative to the total weight of the catalyst, and when the cobalt content is greater than or equal to 2% by weight, the yield of the hydrogenation reaction and its selectivity increase, having values of greater than 50% and greater than 70% in terms of yield and selectivity, respectively.
[0135] When the catalyst CoCu / ZrO2 comprises a greater mass of copper than of cobalt, in particular when the weight ratio of cobalt to copper varies from 1:2 to 1:5, and when the copper content is 10% and the cobalt content is greater than or equal to 2% of the total weight of the catalyst and the specific surface area of the catalyst is 1 m 2 / g to 10m 2 / g, the yield and selectivity of the hydrogenation reaction are improved, with values of more than 70% and more than 80% in terms of yield and selectivity, respectively.
[0136] According to a particular embodiment, the invention relates to the use as defined above, in which the mass composition of cobalt and copper of the catalyst is chosen from:
[0137] -Co(2%)Cu(10%);
[0138] -Co(5%)Cu(10%),
[0139] -Co(5%)Cu(5%),
[0140] - and Co(10%)Cu(10%),
[0141] Preferably, Co(2%)Cu(10%) and Co(5%)Cu(10%),
[0142] More preferably, Co(5%)Cu(10%).
[0143] The mass composition Co(5%)Cu(10%) corresponds to a Co content of 5% based on the total weight of the catalyst and a Cu content of 10% based on the total weight of the catalyst, ie, a mass ratio of cobalt to copper of 1:2.
[0144] The mass composition Co(5%)Cu(5%) corresponds to a Co content of 5% by weight and a Cu content of 5% by weight, i.e. the ratio of cobalt to copper is 1:1 and the Co content is 5% based on the total weight of the catalyst and the Cu content is 5% based on the total weight of the catalyst.
[0145] According to a specific embodiment, the present invention relates to the use as defined above, wherein the mass composition of cobalt and copper of the catalyst is selected from Co(2%)Cu(10%), Co(5%)Cu(10%), more preferably Co(5%)Cu(10%), wherein the mass content of copper is greater than the mass content of cobalt.
[0146] According to a specific embodiment, the present invention relates to the use as defined above, wherein the mass composition of cobalt and copper of the catalyst is Co (5%) Cu (10%) and the specific surface area is 1m 2 / g to 10m 2 / g.
[0147] According to a particular embodiment, the invention relates to the use as defined above, wherein the mass composition of cobalt and copper of the catalyst varies from Co(2%)Cu(10%) to Co(10%)Cu(10%).
[0148] According to a particular embodiment, the present invention relates to the use as defined above, wherein:
[0149] - a total content of elemental copper of 5 to 10% by weight, based on the total weight of the catalyst, in particular 10% by weight, based on the total weight of the catalyst,
[0150] - and a total content of elemental cobalt of 2% to 10% by weight, based on the total weight of the catalyst,
[0151] In particular, 5% by weight based on the total weight of the catalyst.
[0152] According to a particular embodiment, the invention relates to the use as defined above, wherein the mass composition of cobalt and copper of the catalyst varies from Co(2%)Cu(10%) to Co(5%)Cu(10%).
[0153] According to a particular embodiment, the present invention relates to the use as defined above, wherein:
[0154] - the total content of copper element is 10% based on the total weight of the catalyst,
[0155] - and the total content of cobalt elements is 2% to 5% based on the total weight of the catalyst, in particular 5% based on the total weight of the catalyst.
[0156] According to a particular embodiment, the present invention relates to the use as defined above, wherein:
[0157] - the total content of copper element is 10% based on the total weight of the catalyst,
[0158] - the total content of cobalt is 2% to 5% by weight of the total catalyst, in particular 5% by weight of the total catalyst,
[0159] - and the specific surface area of the catalyst was 1 m 2 / g to 50m 2 / g,
[0160] Preferably, 1m 2 / g to 10m 2 / g.
[0161] Using catalysts with Cu and Co surface characteristics
[0162] According to a particular embodiment, the invention relates to the use as defined above, wherein the catalyst has a molar amount of elemental copper in oxidation degree (II) and / or elemental cobalt in oxidation degree (II) greater than 50%.
[0163] The present inventors have unexpectedly found that for the hydrogenation of oxalate esters to ethylene glycol, a CoCu / ZrO2 bimetallic catalyst can be used directly after preparation by calcination in air, without any prior reduction step of the copper and cobalt atoms under hydrogen before using the catalyst in the hydrogenation reaction.
[0164] Advantageously, in some cases, the use of a catalyst in which a substantial portion of the copper and cobalt elements are already present in an oxidized state allows the catalyst to be used prior to carrying out the hydrogenation reaction of the oxalate to ethylene glycol, without prior reduction of the copper and cobalt elements in the catalyst. This also avoids the need to store the catalyst in an inert atmosphere to prevent oxidation of the copper and cobalt atoms.
[0165] According to a particular embodiment, the invention relates to the use as defined above, wherein the catalyst has a molar amount of greater than 50% of elemental copper in oxidation degree (II) and greater than 50% of elemental cobalt in oxidation degree (II).
[0166] According to a particular embodiment, the invention relates to the use as defined above, wherein the catalyst has a molar amount of greater than 70% of elemental copper in degree of oxidation (II) and greater than 65% of elemental cobalt in degree of oxidation (II).
[0167] According to a specific embodiment, the invention relates to the use as defined above, wherein the catalyst has a molar amount of greater than 50% of elemental copper in oxidation degree (II) in the form of CuO and greater than 50% of elemental cobalt in oxidation degree (II) in the form of Co2O3 or Co(OH)2.
[0168] According to a particular embodiment, the invention relates to the use as defined above, wherein the catalyst has a molar amount of greater than 70% of elemental copper in oxidation degree (II) in the form of CuO and a molar amount of greater than 65% of elemental cobalt in oxidation degree (II) in the form of Co2O3 or Co(OH)2.
[0169] According to a specific embodiment, the present invention relates to the use as described above, wherein the catalyst has:
[0170] - from 10 to 30% by mole of elemental copper in the metallic state in oxidation degree (0) or in the form of Cu2O in oxidation degree (I),
[0171] - and from 10 to 35% by mole of elemental cobalt in the metallic state in the oxidation state (0).
[0172] According to a specific embodiment, the present invention relates to the use as described above, wherein the catalyst has:
[0173] - a molar amount of more than 70% of elemental copper in the form of CuO in oxidation degree (II),
[0174] - from 10 to 30% by mole of elemental copper in the metallic state in oxidation degree (0) or in the form of Cu2O in oxidation degree (I),
[0175] - from 10 to 35% by mole of elemental cobalt in the metallic state at the oxidation degree (0),
[0176] - and more than 65% by molar amount of elemental cobalt in the form of Co2O3 or Co(OH)2 in oxidation degree (II).
[0177] Using catalysts with specific morphologies
[0178] According to a particular embodiment, the invention relates to the use as defined above, wherein the catalyst is in the form of a population of micronized particles ranging from 1 μm to 500 μm.
[0179] The range of 1 μm to 500 μm includes the following ranges: 1 μm to 50 μm; 50 μm to 100 μm; 100 μm to 200 μm; 200 μm to 300 μm; 300 μm to 400 μm.
[0180] "Particles" refer to distinct clusters that have either visual or mechanical consistency.
[0181] According to a particular embodiment, the invention relates to the use as defined above, wherein the catalyst is in the form of a population of particles having a rounded morphology.
[0182] For the purposes of the present invention, "rounded particles" refer to particles that have no edges, angles, or bevels.
[0183] Use hydrogenation selectivity
[0184] The selectivity of a chemical reaction refers to the amount of desired product formed relative to the number of moles of the limiting reactant consumed. It indicates whether multiple reactions are occurring in parallel, producing unwanted byproducts, or whether the reaction being performed is the only one consuming the reactant.
[0185] In the case of the hydrogenation step, the selectivity is defined as the amount of ethylene glycol obtained relative to the total amount of products obtained (including minor by-products produced by the conversion of the oxalate compound and ethylene glycol).
[0186] The term "selective reaction" refers to a reaction that produces the target product ethylene glycol with a selectivity greater than 50%.
[0187] According to a particular embodiment, the invention relates to the use as defined above, wherein the hydrogenation of the oxalate compound by hydrogen to obtain ethylene glycol is selective, with a selectivity greater than 70%.
[0188] According to a particular embodiment, the invention relates to the use as defined above, wherein the hydrogenation of the oxalate compound by hydrogen to obtain ethylene glycol is selective, with a selectivity greater than 80%.
[0189] According to a particular embodiment, the invention relates to the use as defined above, wherein the hydrogenation of the oxalate compound by hydrogen to obtain ethylene glycol is selective, with a selectivity greater than 90%.
[0190] According to a particular embodiment, the invention relates to the use as defined above, wherein the hydrogenation of the oxalate compound by hydrogen to obtain ethylene glycol is selective, with a selectivity greater than or equal to 95%.
[0191] The yield of hydrogenation reaction
[0192] Chemical yield reflects the efficiency of the chemical reaction being studied. Yield refers to the ratio of the amount of product obtained to the maximum amount that can be obtained when the reaction is complete.
[0193] The yield of the hydrogenation reaction of oxalate esters to ethylene glycol according to the present invention is determined as the mole percentage of ethylene glycol obtained per mole of oxalate ester.
[0194] The yield of the hydrogenation of oxalic acid ester to ethylene glycol can be determined in particular using gas chromatography coupled to a mass spectrometer (GC-MS), with mesitylene being used as an internal standard.
[0195] According to a particular embodiment, the invention relates to the use as defined above, wherein the hydrogenation of the oxalate compound by hydrogen to obtain ethylene glycol has a yield greater than 50%, in particular greater than 70%, preferably greater than 80%.
[0196] According to a particular embodiment, the present invention relates to the use as defined above, wherein the hydrogenation of the oxalate compound by hydrogen to obtain ethylene glycol is selective, said selectivity being greater than 70%, preferably greater than 90%, more preferably greater than or equal to 95%,
[0197] And / or wherein the hydrogenation reaction of the oxalate compound with hydrogen to obtain ethylene glycol has a yield greater than 70%, preferably greater than 80%.
[0198] catalyst
[0199] A second object of the present invention relates to a supported bimetallic catalyst having the formula CoCu / ZrO2, said catalyst comprising copper and cobalt on a zirconium dioxide support,
[0200] The catalyst has a surface area of 1 m 2 / g to 250m 2 / g.
[0201] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein said catalyst has a surface area of 1 m 2 / g to 75m 2 / g, preferably, 1m 2 / g to 50m 2 / g.
[0202] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein said catalyst has a surface area of 1 m 2 / g to 250m 2 / g,
[0203] And wherein the catalyst includes a crystalline phase, which is crystallized in a monoclinic system according to X-ray diffraction analysis.
[0204] Specific surface area
[0205] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein said catalyst has a surface area of 1 m 2 / g to 50m 2 / g.
[0206] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein said catalyst has a surface area of 1 m 2 / g to 10m 2 / g, preferably about 5m 2 / g.
[0207] structure
[0208] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein said crystalline phase represents 50% to 90% of the total weight of said catalyst.
[0209] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein the crystalline phase is baddeleyite.
[0210] According to a particular embodiment, the present invention relates to a bimetallic catalyst as defined above, wherein said zirconium dioxide support comprises a crystalline phase, crystallized in the monoclinic system as analyzed by X-ray diffraction.
[0211] According to a particular embodiment, the invention relates to a bimetallic catalyst as defined above, said crystalline phase representing from 50% to 90% of the total weight of said catalyst.
[0212] The range of 50% to 90% includes the following ranges: 50% to 55%, 55% to 60%, 60% to 65%, 65% to 70%, 70% to 75%, 75% to 80%, 80% to 85%, and 85% to 90%.
[0213] According to a particular embodiment, the invention relates to a bimetallic catalyst as defined above, wherein said crystalline phase is baddeleyite.
[0214] Advantageously, the catalyst according to the invention comprises from 50% to 90% baddeleyite.
[0215] Advantageously, the zirconium dioxide catalyst support according to the invention consists of more than 50% baddeleyite, in particular 50% to 100% baddeleyite.
[0216] According to a particular embodiment, the present invention relates to a bimetallic catalyst as defined above, wherein said catalyst comprises a crystalline phase comprising a crystallite size comprised between 15 nm and 100 nm, as analyzed by X-ray diffraction.
[0217] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein the catalyst support made of zirconium dioxide ZrO2 comprises impurities such as hafnium (Hf), rhenium (Re) and silicon (Si) atoms.
[0218] Advantageously, the mass ratio between hafnium atoms and zirconium atoms (Hf / Zr) is less than 5%.
[0219] Advantageously, the mass ratio between rhenium atoms and zirconium atoms (Re / Zr) is less than 5%.
[0220] Advantageously, the mass percentage between silicon atoms and zirconium atoms (Si / Zr) is less than 2%.
[0221] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein said catalyst has a microstructure with a crystallite size ranging from 15 nm to 100 nm, preferably from 15 nm to 50 nm.
[0222] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein:
[0223] The catalyst has a surface area of 1 m 2 / g to 250
[0224] m 2 / g, especially 1m 2 / g to 50m 2 / g, preferably, 1m 2 / g to 10m 2 / g,
[0225] - The catalyst comprises a crystalline phase, which is crystallized in a monoclinic system according to X-ray diffraction analysis.
[0226] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein:
[0227] The catalyst has a surface area of 1 m 2 / g to 10
[0228] m 2 / g,
[0229] - and the catalyst comprises a crystalline phase, which is crystallized as monoclinic zircon by X-ray diffraction analysis, and the crystallite size thereof is 15 nm to 100 nm, preferably 15
[0230] nm to 50nm,
[0231] - and includes impurities such as hafnium (Hf), rhenium (Re), and silicon (Si) atoms.
[0232] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst having the formula CoCu / ZrO2 as defined above, comprising copper and cobalt on a zirconium dioxide support,
[0233] The catalyst has a surface area of 1 m 2 / g to 250m 2 / g, preferably, 1m 2 / g to 50m 2 / g, preferably, 1m 2 / g to 10m 2 / g, especially about 5m 2 / g,
[0234] And wherein, the catalyst includes a crystalline phase, which is monoclinic crystallized by X-ray diffraction analysis, especially the crystalline phase accounts for 50% to 90% of the total weight of the catalyst, preferably, the crystalline phase is baddeleyite, and preferably it includes a grain size of 15nm to 100nm.
[0235] composition
[0236] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein said catalyst comprises the bimetallic elements copper and cobalt in a total content ranging from 0.5% to 25% by weight based on the total weight of the catalyst.
[0237] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein said catalyst comprises a total content of the bimetallic elements copper and cobalt of 5% to 20%.
[0238] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein the total content of elemental copper is from 1% to 25% by weight of the total catalyst, preferably from 1% to 10% by weight of the total catalyst.
[0239] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein the total content of elemental cobalt is from 1% to 25% by weight of the total catalyst, preferably from 1% to 10% by weight of the total catalyst.
[0240] According to a particular embodiment, the invention relates to a catalyst as defined above, in which the mass of cobalt is greater than the mass of copper.
[0241] According to a particular embodiment, the invention relates to a catalyst as defined above, in which the weight ratio of copper to cobalt varies from 1:1 to 1:10, in particular from 1:1 to 1:5.
[0242] According to a particular embodiment, the invention relates to a catalyst as defined above, wherein the mass composition of cobalt and copper of the catalyst is chosen from Co(10%)Cu(5%) and Co(15%)Cu(5%).
[0243] In a particular embodiment, the invention relates to a catalyst as defined above, wherein the mass of copper is greater than the mass of cobalt.
[0244] According to a particular embodiment, the invention relates to a supported bimetallic catalyst as defined above, wherein the weight ratio between cobalt and copper varies from 1:1 to 1:10.
[0245] According to a particular embodiment, the invention relates to a supported bimetallic catalyst as defined above, wherein the weight ratio between cobalt and copper varies from 1:1 to 1:5.
[0246] According to a particular embodiment, the invention relates to a supported bimetallic catalyst as defined above, in which the weight ratio between cobalt and copper varies from 2:10 to 5:10.
[0247] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein the mass composition of cobalt and copper of the catalyst is selected from the group consisting of:
[0248] -Co(2%)Cu(10%);
[0249] -Co(5%)Cu(10%),
[0250] -Co(5%)Cu(5%),
[0251] - and Co(10%)Cu(10%),
[0252] Preferably, Co(2%)Cu(10%) and Co(5%)Cu(10%),
[0253] More preferably, Co(5%)Cu(10%).
[0254] According to a specific embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein the mass composition of cobalt and copper of the catalyst is selected from Co(2%)Cu(10%) and Co(5%)Cu(10%), more preferably Co(5%)Cu(10%), wherein the mass content of copper is greater than the mass content of cobalt.
[0255] According to a specific embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein the mass composition of cobalt and copper of the catalyst is Co (5%) Cu (10%) and the specific surface area is 1m 2 / g to 10m 2 / g.
[0256] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein the mass composition of cobalt and copper of the catalyst varies from Co(2%)Cu(10%) to Co(10%)Cu(10%).
[0257] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein
[0258] - a total content of elemental copper of 5 to 10% by weight, based on the total weight of the catalyst, in particular 10% by weight, based on the total weight of the catalyst,
[0259] - and a total content of elemental cobalt of 2% to 10% by weight, based on the total weight of the catalyst,
[0260] In particular, 5% by weight based on the total weight of the catalyst.
[0261] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein the mass composition of cobalt and copper of the catalyst varies from Co(2%)Cu(10%) to Co(5%)Cu(10%).
[0262] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein:
[0263] - the total content of copper element is 10% based on the total weight of the catalyst,
[0264] - and the total content of cobalt elements is 2% to 5% based on the total weight of the catalyst, in particular 5% based on the total weight of the catalyst.
[0265] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein:
[0266] - the total content of cobalt is 2% to 5% by weight of the total catalyst, in particular 5% by weight of the total catalyst,
[0267] - and the specific surface area of the catalyst was 1 m 2 / g to 50m 2 / g,
[0268] Preferably, 1m 2 / g to 10m 2 / g.
[0269] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein:
[0270] - the total content of cobalt is 2% to 5% by weight of the total catalyst, in particular 5% by weight of the total catalyst,
[0271] -The specific surface area of the catalyst was 1 m 2 / g to 50m 2 / g, preferably, 1m 2 / g to 10m 2 / g,
[0272] - and comprising a crystalline phase, which, by X-ray diffraction analysis, is a monoclinic crystal, in particular a baddeleyite crystal, and whose size is preferably 15 nm to 100 nm, preferably
[0273] 15nm to 50nm, and specifically includes hafnium, rhenium and silicon impurities.
[0274] Oxidation degree of Co and Cu on the surface
[0275] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein said catalyst has a molar amount of elemental copper in oxidation degree (II) and / or elemental cobalt in oxidation degree (II) greater than 50%.
[0276] Advantageously, the bimetallic catalyst allows its use before carrying out the hydrogenation reaction of oxalate to ethylene glycol without prior reduction of the copper and cobalt elements of the catalyst: the majority of the elemental copper and cobalt are already present in an oxidized state. This also makes it possible to avoid storing the catalyst in an inert atmosphere to avoid oxidation of the copper and cobalt atoms.
[0277] According to a particular embodiment, the invention relates to a catalyst as defined above, wherein said catalyst has a molar amount of greater than 50% of elemental copper in oxidation degree (II) and greater than 50% of elemental cobalt in oxidation degree (II).
[0278] According to a particular embodiment, the invention relates to a catalyst as defined above, wherein said catalyst has a molar amount of greater than 70% of elemental copper in oxidation degree (II) and greater than 65% of elemental cobalt in oxidation degree (II).
[0279] According to a specific embodiment, the present invention relates to a catalyst as defined above, wherein the catalyst has a molar amount of greater than 50% of elemental copper in oxidation degree (II) in the form of CuO and greater than 50% of elemental cobalt in oxidation degree (II) in the form of Co2O3 or Co(OH)2.
[0280] According to a specific embodiment, the present invention relates to a catalyst as defined above, wherein the catalyst has a molar amount of more than 70% of elemental copper in oxidation degree (II) in the form of CuO and a molar amount of more than 65% of elemental cobalt in oxidation degree (II) in the form of Co2O3 or Co(OH)2.
[0281] According to a specific embodiment, the present invention relates to a catalyst as described above, wherein the catalyst has:
[0282] - from 10 to 30 molar % of elemental copper in the metallic state in an oxidized form
[0283] (0), or in the form of Cu2O in oxidation degree (I),
[0284] - and from 10 to 35% by mole of elemental cobalt in the metallic state in the oxidation state (0).
[0285] According to a specific embodiment, the present invention relates to a catalyst as described above, wherein the catalyst has:
[0286] - greater than 70% by mole of elemental copper in the form of CuO in an oxidized state
[0287] (II),
[0288] - from 10 to 30 molar % of elemental copper in the metallic state in an oxidized form
[0289] (0), or in the form of Cu2O in oxidation degree (I),
[0290] - from 10 to 35 molar % of elemental cobalt in the metallic state in an oxidized form
[0291] (0),
[0292] - and more than 65% by molar amount of elemental cobalt in the form of Co2O3 or Co(OH)2 in oxidation degree (II).
[0293] According to a particular embodiment, the present invention relates to a catalyst as defined above, wherein said catalyst has:
[0294] - a molar amount of more than 50% of elemental copper in oxidation state (II) and more than 50% of elemental cobalt in oxidation state (II),
[0295] -Specific surface area is 1m 2 / g to 50m 2 / g,
[0296] - The crystalline phase was analyzed by X-ray diffraction and was found to be monoclinic.
[0297] According to a particular embodiment, the present invention relates to a catalyst as defined above, wherein said catalyst has:
[0298] - a molar amount of more than 70% of elemental copper in the form of CuO in oxidation degree (II),
[0299] - from 10 to 30% by mole of elemental copper in the metallic state in oxidation degree (0) and in the form of Cu2O in oxidation degree (I),
[0300] - from 10 to 35% by mole of elemental cobalt in the metallic state at the oxidation degree (0),
[0301] - more than 65% by molar amount of elemental cobalt in the form of Co2O3 or Co(OH)2 in oxidation degree (II),
[0302] -Specific surface area is 1m by BET analysis 2 / g to 50m 2 / g, especially 1
[0303] m 2 / g to 10m 2 / g,
[0304] - and a crystalline phase, analyzed by X-ray diffraction, crystallizing in the monoclinic system, in particular baddeleyite, including in particular impurities of hafnium, rhenium and silicon.
[0305] Advantageously, in the catalyst defined:
[0306] - the mass ratio between hafnium atoms and zirconium atoms (Hf / Zr) is less than 5%,
[0307] - the mass ratio between rhenium atoms and zirconium atoms (Re / Zr) is less than 5%,
[0308] - and the mass ratio between silicon atoms and zirconium atoms (Si / Zr) is less than 2%.
[0309] form
[0310] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein said catalyst is in the form of micronized particles ranging from 1 μm to 500 μm.
[0311] These particles consist in particular of agglomerates of rods having a length to thickness ratio of 1 to 10 and an average thickness of 50 nm to 500 nm.
[0312] As a non-limiting example, morphology and average size can be assessed by scanning electron microscopy (SEM).
[0313] The micron size makes the catalyst easier to handle.
[0314] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein the catalyst comprises the bimetallic elements copper and cobalt in a total content of 0.5% to 25% by weight of the total weight of the catalyst, preferably the weight ratio between cobalt and copper varies from 1:1 to 1:10, preferably from 1:1 to 1:5,
[0315] In particular, the mass composition of cobalt and copper of the catalyst is selected from:
[0316] -Co(2%)Cu(10%),
[0317] -Co(5%)Cu(10%),
[0318] -Co(5%)Cu(5%),
[0319] - and Co(10%)Cu(10%),
[0320] Preferably, Co(2%)Cu(10%) and Co(5%)Cu(10%),
[0321] More preferably, Co(5%)Cu(10%),
[0322] and / or wherein the catalyst has a molar amount of elemental copper in oxidation degree (II) and / or elemental cobalt in oxidation degree (II) greater than 50%,
[0323] And / or wherein the catalyst is in the form of a population of micronized particles ranging from 1 μm to 500 μm, preferably in the form of a population of particles having a rounded morphology.
[0324] Characteristics of catalysts under reducing atmosphere
[0325] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein said catalyst is analyzed by performing a temperature-programmed reduction (TPR) in a dihydrogen reducing atmosphere at a temperature ranging from 30°C to 900°C, characterized in that the reduction temperature of metallic copper with a degree of oxidation (0) ranges from 150°C to 250°C.
[0326] Advantageously, said reduction temperature of metallic copper lies in a temperature range of 170°C to 180°C, preferably 174°C.
[0327] Advantageously, at a temperature above said reduction temperature of metallic copper, in particular at least 10° C. above, more than 80%, in particular 80% to 100%, preferably 100%, of the copper atoms are in metallic form.
[0328] The range of 80% to 100% includes the following ranges: 80% to 85%, 85% to 90%, 90% to 95%, 95% to 96%, 96% to 97%, 97% to 98%, 98% to 99%, and 99% to 100%.
[0329] Advantageously, at a temperature above said reduction temperature of metallic copper, in particular at least 10° C. above, 80% to 100%, preferably 100%, of the cobalt atoms are in an oxidized state, ie at a degree of oxidation greater than zero.
[0330] Advantageously, at a temperature above said reduction temperature of metallic copper, in particular at least 10° C. above, 0% to 20%, in particular 0% to 10%, preferably less than 5% of the cobalt atoms are in the metallic state with zero oxidation degree.
[0331] The range of 0% to 20% includes the following values: 0.0%, 0.05%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%.
[0332] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein said catalyst is analyzed by performing a temperature-programmed reduction (TPR) in a dihydrogen reducing atmosphere at a temperature ranging from 30°C to 900°C, characterized in that the reduction temperature of metallic copper with a degree of oxidation (0) ranges from 150°C to 250°C,
[0333] In particular at a temperature at least 10° C. higher than said reduction temperature of metallic copper analyzed by TPR,
[0334] 80% to 100%, preferably 100%, of the copper atoms are in metallic form,
[0335] 80% to 100%, preferably 100%, of the cobalt atoms are in oxidized form,
[0336] According to a specific embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein the catalyst is analyzed by performing temperature-programmed reduction (TPR) in a reducing atmosphere of a 5 vol% H2 flow in argon (especially at 30 mL / min) in a temperature range of 30°C to 900°C, especially at a heating rate of 5°C / min, characterized in that the reduction temperature of metallic copper with degree of oxidation (0) is in the range of 150°C to 250°C.
[0337] Advantageously, before said analysis, the catalyst is pretreated in an inert atmosphere, in particular under helium, at 200°C.
[0338] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein, in a reducing atmosphere comprising hydrogen, at a pressure of 2 MPa to 10 MPa and a temperature of 150° C. to 250° C. (in particular 180° C. to 220° C.), the catalyst comprises:
[0339] 80% to 100%, in particular 95% to 100%, preferably 100%, of metallic copper atoms Cu(0), and
[0340] - 80% to 100% of the cobalt atoms are in a degree of oxidation greater than zero.
[0341] Advantageously, 95%, preferably 100%, of the copper atoms are in metallic form.
[0342] Advantageously, 80% to 100%, in particular 95% to 100%, preferably 100%, of the cobalt atoms are in oxidized form with a degree of oxidation greater than zero.
[0343] Advantageously, 0% to 20%, in particular 0% to 15%, preferably less than 20%, of the cobalt atoms are in metallic form.
[0344] Preparation method of ethylene glycol
[0345] A third object of the present invention relates to a method for preparing ethylene glycol, comprising:
[0346] - a hydrogenation step of an oxalate compound to ethylene glycol by hydrogen in the presence of a supported bimetallic catalyst having the formula CoCu / ZrO2, comprising copper and cobalt on a zirconium dioxide support.
[0347] According to a specific embodiment, the present invention relates to the preparation method as defined above, wherein the oxalate compound has the following formula 1:
[0348]
[0349] Among them, R a express:
[0350] C1 to C 20 a straight-chain or branched alkyl group,
[0351] C3 to C 10 cycloalkyl groups,
[0352] C3 to C 20 an aryl or heteroaryl group,
[0353] C5 to C 20 Alkyl-aryl or alkyl-heteroaryl groups.
[0354] According to a specific embodiment, the present invention relates to a method for preparing ethylene glycol as defined above, wherein the oxalate compound is selected from dimethyl oxalate, diethyl oxalate, diphenyl oxalate, dibenzyl oxalate, isopropyl oxalate and di-tert-butyl oxalate.
[0355] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein:
[0356] The hydrogenation step includes:
[0357] - contacting, to obtain a reaction medium which can be pressurized:
[0358] - the oxalate compound,
[0359] -dihydrogen,
[0360] - said supported catalyst having the formula CoCu / ZrO2, said catalyst comprising cobalt and copper on a zirconium dioxide support,
[0361] - optionally a solvent,
[0362] - optionally, heating the reaction medium,
[0363] to obtain ethylene glycol.
[0364] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein:
[0365] The hydrogenation step includes
[0366] - contacting the following to obtain a reaction medium:
[0367] - the oxalate compound,
[0368] -dihydrogen,
[0369] - said supported catalyst having the formula CoCu / ZrO2, said catalyst comprising cobalt and copper on a zirconium dioxide support,
[0370] - solvent,
[0371] - optionally, heating the reaction medium,
[0372] to obtain ethylene glycol.
[0373] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein:
[0374] The hydrogenation step includes
[0375] - contacting the following to obtain a reaction medium:
[0376] --the oxalate compound,
[0377] -dihydrogen,
[0378] - said supported catalyst having the formula CoCu / ZrO2, said catalyst comprising cobalt and copper on a zirconium dioxide support,
[0379] - solvent,
[0380] - heating the reaction medium,
[0381] to obtain ethylene glycol.
[0382] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein:
[0383] The hydrogenation step includes
[0384] - contacting the following substances to obtain a reaction medium under pressure:
[0385] --the oxalate compound,
[0386] -dihydrogen,
[0387] - said supported catalyst having the formula CoCu / ZrO2, said catalyst comprising copper and cobalt on a zirconium dioxide support,
[0388] - solvent,
[0389] - heating the reaction medium
[0390] to obtain ethylene glycol.
[0391] According to a specific embodiment, the present invention relates to a method for preparing ethylene glycol as defined above, wherein the oxalate is selected from dimethyl oxalate, diethyl oxalate, dibenzyl oxalate, di-tert-butyl oxalate, diisopropyl oxalate, and diphenyl oxalate.
[0392] According to a specific embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the oxalate is selected from dimethyl oxalate and diethyl oxalate, preferably diethyl oxalate.
[0393] Advantageously, the oxalic acid esters used are obtainable by carbonylation of alcohols in the presence of CO and oxygen.
[0394] Advantageously, the carbon monoxide CO used for the preparation of oxalate esters is produced by electrolysis of carbon dioxide CO 2 to carbon monoxide CO.
[0395] Therefore, the synthesis of ethylene glycol is advantageously carried out from the recovered CO2 and alcohol.
[0396] Method for preparing ethylene glycol using a catalyst
[0397] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the catalyst is a catalyst according to the present invention as defined above.
[0398] According to a particular embodiment, the invention relates to a process for the preparation of ethylene glycol as defined above, wherein the catalyst is prepared by mixing the support in powder form with an aqueous solution of copper and cobalt salts, followed by calcination.
[0399] According to a particular embodiment, the invention relates to a process for the preparation of ethylene glycol as defined above, wherein the catalyst is prepared by mixing the support in powder form with an aqueous solution of copper and cobalt salts, without adding additives or surfactants, followed by calcination.
[0400] Advantageously, the catalyst used in the process as defined above is prepared according to a preparation process comprising the following steps:
[0401] Step A: Dissolve in an aqueous solution (5 mL to 10 mL by volume of water)
[0402] The cobalt salt and copper salt are impregnated on a zirconium dioxide support in powder form, with the ratio of the mass of the solution to the mass of the support being 0.6 to 1.0;
[0403] To obtain the catalyst CoCu / ZrO2 in the form of a homogeneous mixture,
[0404] Step B, drying the homogeneous mixture to obtain the catalyst CoCu / ZrO2 in the form of a dried homogeneous mixture,
[0405] • An activation step C, comprising calcining said dried homogeneous mixture to obtain said catalyst.
[0406] Advantageously, during the impregnation step A, the aqueous solution containing the cobalt and copper salts is free of additives and surfactants. In other words, the aqueous impregnation solution consists of a demineralized aqueous solution in which the cobalt and copper salts are dissolved.
[0407] Advantageously, the cobalt salt is cobalt nitrate and the copper salt is copper nitrate.
[0408] Thus, the process for preparing ethylene glycol according to the invention, as defined above, is carried out with a catalyst prepared from an aqueous solution, advantageously free of additives and surfactants, making it more industrializable and less costly.
[0409] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the catalyst has a surface area of 1 m 2 / g to 250m 2 / g.
[0410] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the catalyst has a surface area of 1 m 2 / g to 50m 2 / g.
[0411] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the catalyst has a surface area of 1 m 2 / g to 10m 2 / g, preferably about 5m 2 / g.
[0412] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the catalyst comprises a crystalline phase which, as determined by X-ray diffraction analysis, crystallizes in the monoclinic system.
[0413] According to a particular embodiment, the invention relates to a process for the preparation of ethylene glycol as defined above, wherein said crystalline phase of the catalyst represents 50% to 90% of the total weight of the catalyst.
[0414] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the crystalline phase is baddeleyite.
[0415] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the grain size of the crystalline phase is between 15 nm and 40 nm.
[0416] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the zirconium dioxide support of the CoCu / ZrO2 catalyst comprises baddeleyite in an amount ranging from 50% to 90% by weight relative to the total weight of the catalyst.
[0417] The range of 50% to 90% includes the following ranges: 50% to 55%, 55% to 60%, 60% to 65%, 65% to 70%, 70% to 75%, 75% to 80%, 80% to 85%, and 85% to 90%.
[0418] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the catalyst comprises the bimetallic elements copper and cobalt in a total content ranging from 0.5% to 25% by weight of the total catalyst.
[0419] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the catalyst comprises the bimetallic elements copper and cobalt in a total content ranging from 5% to 20%.
[0420] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the total content of elemental copper is between 1% and 25% by weight of the total catalyst, preferably between 1% and 10% by weight of the total catalyst.
[0421] According to a particular embodiment, the invention relates to a process for the preparation of ethylene glycol as defined above, wherein the total content of elemental cobalt is between 1% and 25% by weight of the total catalyst, preferably between 1% and 10% by weight of the total catalyst.
[0422] In a particular embodiment, the invention relates to a process for the preparation of ethylene glycol as defined above, wherein the mass of cobalt is greater than the mass of copper.
[0423] According to a particular embodiment, the invention relates to a process for the preparation of ethylene glycol as defined above, wherein the weight ratio of copper to cobalt varies from 1:1 to 1:10, in particular from 1:1 to 1:5.
[0424] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the mass composition of cobalt and copper of the catalyst is chosen from Co(10%)Cu(5%) and Co(15%)Cu(5%).
[0425] According to a particular embodiment, the invention relates to a process for the preparation of ethylene glycol as defined above, wherein the mass of copper is greater than the mass of cobalt.
[0426] According to a particular embodiment, the invention relates to a process for the preparation of ethylene glycol as defined above, wherein the catalyst has a weight ratio between cobalt and copper varying from 1:1 to 1:10.
[0427] According to a particular embodiment, the invention relates to a process for preparing ethylene glycol as defined above, wherein the catalyst has a weight ratio between cobalt and copper varying from 2:10 to 5:10.
[0428] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the mass composition of the cobalt and copper of the catalyst is selected from:
[0429] -Co(2%)Cu(10%),
[0430] -Co(5%)Cu(10%),
[0431] -Co(5%)Cu(5%),
[0432] - and Co(10%)Cu(10%),
[0433] Preferably, Co(2%)Cu(10%) and Co(5%)Cu(10%),
[0434] More preferably, Co(5%)Cu(10%).
[0435] According to a specific embodiment, the present invention relates to a process for preparing ethylene glycol as defined above, wherein the catalyst comprises bimetallic elements copper and cobalt in an amount of 0.5% to 25% by weight based on the total weight of the catalyst.
[0436] and wherein the weight ratio between cobalt and copper varies from 1:1 to 1:5,
[0437] In particular, the mass composition of cobalt and copper of the catalyst is selected from:
[0438] --Co(2%)Cu(10%),
[0439] -Co(5%)Cu(10%),
[0440] -Co(5%)Cu(5%),
[0441] - and Co(10%)Cu(10%),
[0442] Preferably, Co(2%)Cu(10%) and Co(5%)Cu(10%),
[0443] More preferably, Co(5%)Cu(10%).
[0444] According to a specific embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the mass composition of cobalt and copper of the catalyst is selected from Co(2%)Cu(10%) or Co(5%)Cu(10%), more preferably Co(5%)Cu(10%), wherein the mass of copper is greater than the mass content of cobalt.
[0445] According to a specific embodiment, the present invention relates to a process for preparing ethylene glycol as defined above, wherein the mass composition of cobalt and copper of the catalyst is Co (5%) Cu (10%) and the specific surface area is 1m 2 / g to 10m 2 / g.
[0446] According to a particular embodiment, the invention relates to a process for the preparation of ethylene glycol as defined above, wherein the mass composition of cobalt and copper of the catalyst varies from Co(2%)Cu(10%) to Co(10%)Cu(10%).
[0447] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein, in the catalyst:
[0448] - a total content of elemental copper of 5 to 10% by weight, based on the total weight of the catalyst, in particular 10% by weight, based on the total weight of the catalyst,
[0449] - and a total content of elemental cobalt of 2% to 10% by weight, based on the total weight of the catalyst,
[0450] In particular, 5% by weight based on the total weight of the catalyst.
[0451] According to a particular embodiment, the invention relates to a process for the preparation of ethylene glycol as defined above, wherein the mass composition of cobalt and copper of the catalyst varies from Co(2%)Cu(10%) to Co(5%)Cu(10%).
[0452] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein, in the catalyst:
[0453] - the total content of elemental copper is 10% by weight of the total catalyst,
[0454] - and a total content of elemental cobalt of 2 to 5% by weight, based on the total weight of the catalyst, in particular 5% by weight, based on the total weight of the catalyst.
[0455] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein, in the catalyst:
[0456] - a total content of elemental cobalt of 2 to 5% by weight, based on the total weight of the catalyst, in particular 5% by weight, based on the total weight of the catalyst,
[0457] - and the specific surface area of the catalyst was 1 m 2 / g to 50m 2 / g,
[0458] Preferably, 1m 2 / g to 10m 2 / g.
[0459] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein, in the catalyst:
[0460] - a total content of elemental cobalt of 2 to 5% by weight, based on the total weight of the catalyst, in particular 5% by weight, based on the total weight of the catalyst,
[0461] -The specific surface area of the catalyst was 1 m 2 / g to 50m 2 / g, preferably, 1m 2 / g to 10m 2 / g,
[0462] - and the catalyst comprises a crystalline phase, analyzed by X-ray diffraction, of monoclinic system, in particular baddeleyite, with a crystallite size preferably ranging from 15 nm to 100 nm, in particular from 15 nm to 50 nm, and in particular comprising hafnium, rhenium and silicon impurities.
[0463] According to a particular embodiment, the invention relates to a process for the preparation of ethylene glycol as defined above, wherein the catalyst has a molar amount greater than 50% of elemental copper in oxidation degree (II) and / or elemental cobalt in oxidation degree (II).
[0464] According to a particular embodiment, the invention relates to a process for the preparation of ethylene glycol as defined above, wherein the catalyst has a molar amount of greater than 50% of elemental copper in oxidation degree (II) and greater than 50% of elemental cobalt in oxidation degree (II).
[0465] According to a particular embodiment, the invention relates to a process for the preparation of ethylene glycol as defined above, wherein the catalyst has a molar amount of greater than 70% of elemental copper in oxidation degree (II) and greater than 65% of elemental cobalt in oxidation degree (II).
[0466] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the catalyst has a molar amount of greater than 50% of elemental copper in oxidation degree (II) in the form of CuO and greater than 50% of elemental cobalt in oxidation degree (II) in the form of Co2O3 or Co(OH)2.
[0467] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the catalyst has a molar amount of greater than 70% of elemental copper in oxidation degree (II) in the form of CuO and greater than 65% of elemental cobalt in oxidation degree (II) in the form of Co2O3 or Co(OH)2.
[0468] According to a particular embodiment, the present invention relates to a process for preparing ethylene glycol as defined above, wherein the catalyst has:
[0469] - Elemental copper in the form of Cu2O in a degree of oxidation (I) in an amount of 10 to 30% by mole.
[0470] According to a particular embodiment, the present invention relates to a process for preparing ethylene glycol as defined above, wherein the catalyst has:
[0471] - 10 to 30% by mole of elemental copper in the metallic state at oxidation degree (0) or in the form of Cu2O at oxidation degree (I),
[0472] - and a molar amount of 10% to 35% in the metallic state in the degree of oxidation (0)
[0473] The element cobalt.
[0474] According to a particular embodiment, the present invention relates to a process for preparing ethylene glycol as defined above, wherein the catalyst has:
[0475] - copper in a molar amount of more than 70% in a degree of oxidation (II) in the form of CuO,
[0476] - elemental copper in the form of Cu2O in an oxidation degree (I) of 10 to 30% by mole,
[0477] - and elemental cobalt in a molar amount of greater than 65% in degree of oxidation (II) in the form of Co2O3 or Co(OH)2.
[0478] According to a particular embodiment, the present invention relates to a process for preparing ethylene glycol as defined above, wherein the catalyst has:
[0479] - elemental copper in a degree of oxidation (II) in the form of CuO in a molar amount of more than 70%,
[0480] - 10 to 30% by mole of elemental copper in the metallic state at oxidation degree (0) or in the form of Cu2O at oxidation degree (I),
[0481] - elemental cobalt in the metallic state in a degree of oxidation (0) in a molar amount of 10 to 35%,
[0482] - and elemental cobalt in a molar amount of greater than 65% in degree of oxidation (II) in the form of Co2O3 or Co(OH)2.
[0483] According to a particular embodiment, the present invention relates to a process for preparing ethylene glycol as defined above, wherein the catalyst has:
[0484] - a molar amount of more than 50% of elemental copper in oxidation state (II) and more than 50% of elemental cobalt in oxidation state (II),
[0485] -Specific surface area is 1m 2 / g to 50m 2 / g,
[0486] - The crystalline phase was analyzed by X-ray diffraction and was found to be monoclinic.
[0487] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the catalyst has:
[0488] - elemental copper in a degree of oxidation (II) in the form of CuO in a molar amount of more than 70%,
[0489] - 10 to 30% by mole of elemental copper in the metallic state at oxidation degree (0) and in the form of Cu2O at oxidation degree (I),
[0490] - elemental cobalt in the form of Co2O3 or Co(OH)2 in oxidation degree (II) in an amount of more than 65% by mole,
[0491] -Specific surface area is 1m by BET analysis 2 / g to 50m 2 / g, especially 1
[0492] m 2 / g to 10m 2 / g,
[0493] - and a crystalline phase, analyzed by X-ray diffraction, crystallizing in the monoclinic system, in particular baddeleyite, including in particular impurities of hafnium, rhenium and silicon.
[0494] According to a particular embodiment, the present invention relates to a process for preparing ethylene glycol as defined above, wherein the catalyst has:
[0495] - elemental copper in a degree of oxidation (II) in the form of CuO in a molar amount of more than 70%,
[0496] - 10 to 30% by mole of elemental copper in the metallic state at oxidation degree (0) or in the form of Cu2O at oxidation degree (I),
[0497] - elemental cobalt in the metallic state in a degree of oxidation (0) in a molar amount of 10 to 35%,
[0498] - elemental cobalt in the form of Co2O3 or Co(OH)2 in oxidation degree (II) in an amount of more than 65% by mole,
[0499] -Specific surface area is 1m by BET analysis 2 / g to 50m 2 / g, especially 1
[0500] m 2 / g to 10m 2 / g,
[0501] - and a crystalline phase, analyzed by X-ray diffraction, crystallizing in the monoclinic system, in particular baddeleyite, including in particular impurities of hafnium, rhenium and silicon.
[0502] According to a particular embodiment, the invention relates to a process for the preparation of ethylene glycol as defined above, wherein the catalyst is in the form of micronized particles ranging from 1 μm to 500 μm.
[0503] Conditions for the preparation of ethylene glycol
[0504] According to a particular embodiment, the invention relates to a process for the preparation of ethylene glycol as defined above, wherein the catalyst is used in a proportion of 0.1 mmol to 10 mmol of copper, in particular in a proportion of 4 mmol of Cu.
[0505] The range of 0.1 mmol to 10 mmol includes the following ranges: 0.1 mmol to 0.5 mmol, 0.5 mmol to 1 mmol, 1 mmol to 2 mmol, 2 mmol to 3 mmol, 3 mmol to 4 mmol.
[0506] According to a specific embodiment, the present invention relates to a process for preparing ethylene glycol as defined above, wherein the oxalate compound is used in a ratio of 2 to 400 molar equivalents, in particular 5 equivalents, relative to metallic Cu.
[0507] The range of 2 molar equivalents (eq.) to 400 molar equivalents (eq.) includes the following ranges: 2eq. to 3eq., 3eq. to 4eq., 4eq. to 5eq., 5eq. to 10eq., 10eq. to 50eq., 50eq. to 100eq., 100eq. to 200eq., 200eq. to 300eq., 300eq. to 400eq.
[0508] According to a particular embodiment, the invention relates to a process for the preparation of ethylene glycol as defined above, wherein hydrogen is used at a pressure ranging from 2 MPa to 10 MPa, in particular at 5 MPa.
[0509] The expression MPa corresponds to 10 6 Pascal, which is equivalent to 10 bar.
[0510] The expression "2.0 MPa to 10.0 MPa" corresponds to the following ranges: 2.0 MPa to 2.5 MPa; 2.5 MPa to 3.0 MPa; 3.0 MPa to 3.5 MPa; 3.5 MPa to 4.0 MPa; 4.0 MPa to 4.5 MPa; 4.5 MPa to 5.0 MPa; 5.0 MPa to 5.5 MPa; 5.5 MPa to 6.0 MPa; 6.0 MPa to 6.5 MPa; 6.5 MPa to 7.0 MPa; 7.0 MPa to 7.5 MPa; 7.5 MPa to 8.0 MPa; 8.0 MPa to 8.5 MPa; 8.5 MPa to 9.0 MPa; 9.0 MPa to 9.5 MPa; 9.5 MPa to 10 MPa.
[0511] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the solvent is selected from ethanol, methanol, isopropanol, tetrahydrofuran (THF), 2-methyltetrahydrofuran, toluene and dioxane, in particular ethanol.
[0512] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the solvent is ethanol and the oxalate is diethyl oxalate.
[0513] According to a particular embodiment, the invention relates to a process for the preparation of ethylene glycol as defined above, wherein the reaction medium is placed under a pressure ranging from 2 MPa to 10 MPa, in particular at 5 MPa.
[0514] According to a particular embodiment, the invention relates to a process for the preparation of ethylene glycol as defined above, wherein the reaction medium is heated to a temperature ranging from 100°C to 250°C, in particular from 200°C to 220°C.
[0515] The range of 100°C to 250°C includes the following ranges: 100°C to 150°C, 150°C to 200°C, and 200°C to 250°C.
[0516] According to a particular embodiment, the invention relates to a process for the preparation of ethylene glycol as defined above, wherein the reaction medium is heated for 5 to 24 hours, in particular for 8 to 16 hours.
[0517] Selectivity and efficiency
[0518] According to a specific embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the hydrogenation of the oxalate compound by hydrogen to obtain ethylene glycol is selective, with a selectivity greater than 70%, in particular greater than 80%, preferably greater than 90%, more preferably greater than or equal to 95%.
[0519] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the hydrogenation of the oxalate compound with hydrogen to obtain ethylene glycol has a yield greater than 50%, in particular greater than 70%, preferably greater than 80%.
[0520] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the catalyst is recovered at the end of the hydrogenation step and reused as catalyst in another catalyzed reaction step.
[0521] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein the catalyst is recovered at the end of the hydrogenation step and reused as catalyst in another subsequent hydrogenation step.
[0522] Advantageously, the catalyst recovered at the end of the hydrogenation step can be used in several successive cycles of the hydrogenation step.
[0523] According to a specific embodiment, the present invention relates to a process for preparing ethylene glycol as defined above,
[0524] Among them, hydrogen is used at a pressure of 2 MPa to 10 MPa, particularly 6 MPa.
[0525] wherein the reaction medium is heated to a temperature of 100° C. to 250° C., in particular 180° C. to 220° C., optionally wherein the reaction medium is heated for 5 hours to 24 hours, in particular 8 hours or 16 hours,
[0526] Wherein, during the heating step of the reaction medium, the supported bimetallic catalyst is activated, and the activated catalyst is composed of:
[0527] 80% to 100%, in particular 95% to 100%, preferably 100%, of metallic copper atoms Cu(0) in a zero oxidation state, and
[0528] - 80% to 100% of the cobalt atoms are in a degree of oxidation greater than zero.
[0529] Advantageously, embodiments of the process according to the present invention do not require pre-activation of the catalyst by reducing metal species, but rather activate the catalyst in situ during the process.
[0530] The catalytic substance for the hydrogenation of the oxalate (i.e., metallic copper with a degree of oxidation (0)) is formed in situ. The second metallic element, cobalt, is primarily in oxidized form on the support surface, acting as a promoter for the copper used to catalyze the hydrogenation of the oxalate. Thus, the copper-cobalt bimetallic catalyst can be directly incorporated into the oxalate hydrogenation process according to the present invention without requiring prior reduction to its metallic form to initiate the hydrogenation reaction, unlike many prior art bimetallic catalysts that are inactive in the first reduction step without the catalytic substance.
[0531] Conditions for the flow method
[0532] The method according to the invention can be implemented in a flow chemistry instrument, for example, in a commercial reactor, for example, the "H-Cube" by Thales Nano INC. "or" ” (7 Zahony Street, Graphisoft Park, Building D, H-1031 Budapest, Hungary), or for example the “E-series” or “R-series flow chemistry system” reactors of Vapourtec Ltd (Unit 21 / Park Farm Business Centre / Fornham Pk, Bury Saint Edmunds IP28 6TS, UK).
[0533] Advantageously, the continuous flow process is carried out at a temperature of 100°C to 250°C.
[0534] Advantageously, the continuous flow process is carried out at a pressure of 0.1 MPa to 10 MPa, preferably 5 MPa.
[0535] According to a specific embodiment, the continuous flow process is carried out in a reactor wherein the gas occupies 10% to 90% of the reactor volume.
[0536] The expression "10% to 90%" corresponds to the following ranges: 10% to 20%; 20% to 30%; 30% to 40%; 40% to 50%; 50% to 60%; 60% to 70%; 70% to 80%; 80% to 90%.
[0537] According to a specific embodiment, the continuous flow method is carried out by allowing the contact time between the reagents to be from 1 second to 2 hours, in particular from 1 second to 2 minutes.
[0538] The expression "1 second to 2 hours" corresponds to the following scales: 1 second to 15 seconds; 15 seconds to 30 seconds; 30 seconds to 1 minute; 1 minute to 2 minutes; 2 minutes to 15 minutes; 15 to 30 minutes; 30 minutes to 1 hour; 1 hour to 2 hours.
[0539] According to a specific embodiment, the hydrogenation step of the method is carried out in a continuous flow and comprises means for introducing a hydrogen gas stream into the reactor for contact with the substrate (oxalate).
[0540] According to a particular embodiment, the present invention relates to a process for the preparation of ethylene glycol as defined above, wherein oxalate ester is circulated under flow and / or dihydrogen is circulated under flow, passing through the catalyst or in contact with the catalyst.
[0541] Catalyst preparation method
[0542] A fourth object of the present invention relates to a method for preparing the catalyst CoCu / ZrO2 as defined above according to the present invention, comprising:
[0543] Step A: impregnating a cobalt salt and a copper salt dissolved in an aqueous solution (5 mL to 10 mL by volume of water) without additives and surfactants onto a zirconium dioxide support in powder form, with the ratio of the solution mass to the support mass being 0.6 to 1.0;
[0544] To obtain a CoCu / ZrO2 catalyst in the form of a homogeneous mixture,
[0545] The carrier has
[0546] 1m 2 / g to 250m 2 / g, especially 1m 2 / g to 75m 2 / g, especially 1m 2 / g to 50m 2 / g, preferably 1m 2 / g to 5m 2 / g surface area,
[0547] and comprising a crystalline phase, which is monoclinic crystallized by X-ray diffraction analysis,
[0548] step B, drying the homogeneous material at a temperature of 60° C. to 100° C. for a period of 10 to 24 hours, so as to obtain the catalyst CoCu / ZrO2 in the form of a dry homogeneous mixture,
[0549] • An activation step C comprising calcining said dried homogeneous mixture at a temperature ranging from 200° C. to 1000° C. for a period ranging from 1 hour to 15 hours under air to obtain said catalyst.
[0550] According to a particular embodiment, the invention relates to a process as defined above for preparing the catalyst according to the invention, wherein, in step A, the cobalt salt is cobalt nitrate and / or the copper salt is copper nitrate.
[0551] According to a particular embodiment, the invention relates to a process as defined above for preparing the catalyst according to the invention, wherein, in step A, the support is used in an amount ranging from 1 g to 50 g.
[0552] According to a particular embodiment, the present invention relates to a process as defined above for preparing a catalyst according to the invention, wherein, in step A, the support used has a surface area of 1 m 2 / g to 75m 2 / g.
[0553] According to a particular embodiment, the present invention relates to a process as defined above for preparing a catalyst according to the invention, wherein, in step A, the support used has a surface area of 1 m 2 / g to 50m 2 / g.
[0554] According to a particular embodiment, the present invention relates to a process as defined above for preparing a catalyst according to the present invention, wherein, in step A, the catalyst support used has a surface area of 1 m 2 / g to 10m 2 / g, preferably 5m 2 / g to 7m 2 / g.
[0555] According to a particular embodiment, the invention relates to a process as defined above for preparing the catalyst according to the invention, wherein, in step A, the support used has a crystalline phase representing 50% to 90% by weight of the total catalyst.
[0556] According to a particular embodiment, the invention relates to a process as defined above for preparing the catalyst according to the invention, wherein, in step A, the support used comprises baddeleyite.
[0557] According to a particular embodiment, the present invention relates to a process as defined above for preparing the catalyst according to the invention, wherein, in step A, the support used comprises baddeleyite having a grain size ranging from 15 nm to 100 nm, preferably from 15 nm to 50 nm, and optionally comprising impurities of hafnium (Hf), rhenium (Re) and silicon (Si).
[0558] Advantageously, the mass ratio between hafnium atoms and zirconium atoms (Hf / Zr) in the carrier used is less than 5%.
[0559] Advantageously, the mass ratio between rhenium atoms and zirconium atoms (Re / Zr) in the support used is less than 5%.
[0560] Advantageously, the mass ratio between silicon atoms and zirconium atoms (Si / Zr) in the support used is less than 2%.
[0561] Advantageously, in the ZrO2 carrier:
[0562] - the mass ratio between hafnium atoms and zirconium atoms (Hf / Zr) is less than 5%,
[0563] - the mass ratio between rhenium atoms and zirconium atoms (Re / Zr) is less than 5%,
[0564] - The mass ratio between silicon atoms and zirconium atoms (Si / Zr) is less than 2%.
[0565] According to a particular embodiment, the invention relates to a process for preparing the catalyst according to the invention as defined above, wherein, in step A, the total mass content of the bimetallic elements copper and cobalt is between 0.5% and 25% by weight, based on the total weight of the catalyst.
[0566] According to a particular embodiment, the invention relates to a process as defined above for preparing the catalyst according to the invention, wherein, in step A, the total mass content of the bimetallic elements copper and cobalt is between 5% and 20% by weight, based on the total weight of the catalyst.
[0567] According to a particular embodiment, the present invention relates to a process for preparing the catalyst according to the invention as defined above, wherein, in step A, the total mass content of elemental copper is between 1% and 25% by weight, preferably between 1% and 10% by weight, based on the total weight of the catalyst.
[0568] According to a specific embodiment, the present invention relates to a process for preparing the catalyst according to the invention as defined above, wherein, in step A, the total mass content of elemental cobalt is from 1% to 25% by weight, preferably from 1% to 10% by weight, based on the total weight of the catalyst.
[0569] According to a particular embodiment, the invention relates to a method as defined above, wherein the mass of cobalt is greater than the mass of copper.
[0570] According to a particular embodiment, the invention relates to a process as defined above, wherein, in step A, the weight ratio between copper and cobalt varies from 1:1 to 1:10, in particular from 1:1 to 1:5.
[0571] According to a particular embodiment, the invention relates to a process as defined above, wherein, in step A, the mass composition of cobalt and copper of the catalyst is chosen from Co(10%)Cu(5%) and Co(15%)Cu(5%).
[0572] According to a particular embodiment, the invention relates to a method as defined above, wherein the mass of copper is greater than the mass of cobalt.
[0573] According to a particular embodiment, the invention relates to a process as defined above for preparing the catalyst according to the invention, wherein, in step A, the weight ratio of cobalt to copper varies from 1:1 to 1:10.
[0574] According to a particular embodiment, the invention relates to a process for preparing the catalyst according to the invention as defined above, wherein, in step A, the weight ratio between cobalt and copper varies from 2:10 to 5:10.
[0575] According to a particular embodiment, the invention relates to a process as defined above for preparing the catalyst according to the invention, wherein, in step A, the support is in the form of microparticles ranging from 1 μm to 500 μm.
[0576] According to a particular embodiment, the invention relates to a process as defined above for preparing the catalyst according to the invention, wherein, in step B, the homogeneous mixture is dried at 80° C. for 16 hours.
[0577] According to a particular embodiment, the invention relates to a process as defined above for preparing the catalyst according to the invention, wherein, in step C, the dried homogeneous mixture is calcined at 600° C. for 2 hours.
[0578] Catalyst prepared according to the method of the present invention
[0579] A fifth object of the present invention relates to a supported bimetallic catalyst having the formula CoCu / ZrO2, said catalyst comprising copper and cobalt on a zirconium dioxide support, said catalyst being obtainable by the process for preparing the catalyst as defined above.
[0580] Characteristics of catalysts under reducing atmosphere
[0581] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst prepared according to the invention and as defined above,
[0582] wherein the catalyst is analyzed by temperature programmed reduction (TPR) in a dihydrogen reducing atmosphere at a temperature range of 30°C to 900°C, wherein the reduction temperature of metallic copper with an oxidation degree (0) is in the range of 150°C to 250°C,
[0583] Especially 180°C to 220°C.
[0584] Advantageously, at a temperature above the reduction temperature of metallic copper, in particular at least 10° C. higher, 80% to 100%, in particular 95% to 100%, preferably 100%, of the copper atoms are in metallic form.
[0585] Advantageously, at a temperature above the reduction temperature of metallic copper, in particular at least 10° C. above, more than 80%, in particular 80% to 100%, preferably 100%, of the cobalt atoms are in oxidized form, ie the degree of oxidation is greater than zero.
[0586] Advantageously, at a temperature above said reduction temperature of metallic copper, in particular at least 10° C. above, 0% to 20%, in particular 0% to 10%, preferably less than 5%, of the cobalt atoms are in metallic form with zero oxidation degree.
[0587] According to a particular embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein said catalyst is analyzed by performing a temperature-programmed reduction (TPR) in a dihydrogen reducing atmosphere at a temperature ranging from 30°C to 900°C, characterized in that the reduction temperature of metallic copper with a degree of oxidation (0) ranges from 150°C to 250°C,
[0588] In particular at a temperature at least 10° C. higher than said reduction temperature of metallic copper analyzed by TPR,
[0589] 80% to 100%, preferably 100%, of the copper atoms are in metallic form,
[0590] 80% to 100%, preferably 100%, of the cobalt atoms are in oxidized form.
[0591] According to a specific embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein the catalyst is analyzed by performing temperature-programmed reduction (TPR) in a reducing atmosphere of a 5 vol% H2 flow in argon (especially at 30 mL / min) in a temperature range of 30°C to 900°C, especially at a heating rate of 5°C / min, characterized in that the reduction temperature of metallic copper with degree of oxidation (0) is in the range of 150°C to 250°C.
[0592] Advantageously, before said analysis, the catalyst is pretreated in an inert atmosphere, in particular under helium, at 200°C.
[0593] According to a specific embodiment, the present invention relates to a supported bimetallic catalyst as defined above, wherein, under a reducing atmosphere of hydrogen, at a pressure of 2 MPa to 10 MPa and a temperature of 150° C. to 250° C. (in particular 180° C. to 220° C.), the catalyst comprises:
[0594] 80% to 100%, in particular 95% to 100%, preferably 100%, of metallic copper atoms Cu(0), and
[0595] - 80% to 100% of the cobalt atoms are in a degree of oxidation greater than zero.
[0596] Advantageously, 95%, preferably 100%, of the copper atoms are in metallic form.
[0597] Advantageously, 80% to 100%, in particular 95% to 100%, preferably 100%, of the cobalt atoms are in oxidized form with a degree of oxidation greater than zero.
[0598] Advantageously, 0% to 20%, in particular 0% to 15%, preferably less than 20%, of the cobalt atoms are in metallic form.
[0599] Catalyst in activated form
[0600] Another object of the present invention relates to an activated supported bimetallic catalyst having the formula CuCo / ZrO2, said catalyst comprising copper and cobalt on the surface of a zirconium dioxide support, wherein
[0601] - 80% to 100%, in particular 95% to 100%, preferably 100% of the copper atoms
[0602] is in oxidation state zero Cu(0), and
[0603] - 80% to 100%, in particular 95% to 100%, preferably 100% of the cobalt atoms
[0604] At a degree of oxidation greater than zero.
[0605] The term "activated catalyst" refers to a catalyst in an active form, ie the form of the catalyst during a chemical reaction catalyzed by the catalyst, ie the form comprising catalytic species that initiate catalysis.
[0606] Use of catalyst for ethylene glycol hydrogenolysis or biomass depolymerization
[0607] Another object of the present invention relates to the use of the catalyst CoCu / ZrO2 as defined above according to the invention for the hydrogenolysis of ethylene glycol.
[0608] The inventors unexpectedly observed that, after the hydrogenation reaction of oxalate to ethylene glycol, when oxalate is no longer present as a substrate in the medium, prolonged contact of ethylene glycol with the catalyst CoCu / ZrO according to the present invention leads to hydrogenolysis of ethylene glycol. Advantageously, the hydrogenation reaction of oxalate to ethylene glycol and the hydrogenolysis reaction of ethylene glycol are continuous and separable.
[0609] For the purposes of the present invention, "hydrogenolysis" refers to a reaction in which at least one carbon-carbon (CC) or carbon-heteroatom covalent bond (eg, carbon-oxygen bond) is broken by the action of hydrogen.
[0610] Another object of the present invention relates to a method for hydrogenolysis of ethylene glycol, comprising:
[0611] - a step of contacting ethylene glycol with a heterogeneous supported bimetallic catalyst as defined above, having the formula CoCu / ZrO2, in the presence of hydrogen, said catalyst comprising copper and cobalt on a zirconium dioxide support.
[0612] According to a particular embodiment, the present invention relates to a process for the hydrogenolysis of ethylene glycol as defined above, comprising:
[0613] - contacting, to obtain a reaction medium, optionally pressurized:
[0614] -ethylene glycol,
[0615] - dihydrogen, in particular at 20 bar to 100 bar, preferably at 60 bar,
[0616] - said supported catalyst having the formula CoCu / ZrO2, said catalyst comprising cobalt and copper on a zirconium dioxide support,
[0617] - optionally a solvent, in particular tetrahydrofuran (THF),
[0618] - optionally a base, in particular potassium tert-butoxide (KOtBu),
[0619] - optionally, heating the reaction medium,
[0620] Degradation of ethylene glycol is thereby achieved by breaking at least one carbon-carbon or carbon-oxygen covalent bond.
[0621] Another object of the present invention relates to the use of the CoCu / ZrO2 catalyst as defined above according to the invention for depolymerizing biomass.
[0622] According to a particular embodiment, the invention relates to the use of the catalyst CoCu / ZrO2 as defined above for depolymerizing biomass by hydrogenolysis of the glycol groups present in the compounds constituting said biomass.
[0623] The inventors have surprisingly observed that the catalyst CoCu / ZrO2 according to the invention can catalyze the hydrogenolysis reaction of diol groups present in carbohydrate molecules contained in biomass by breaking carbon-carbon CC or CO bonds.
[0624] In the present invention, "biomass" refers to organic matter of plant (including microalgae), animal, bacterial, or fungal origin that can be used as an energy source (bioenergy). Biomass includes carbohydrate molecules or polyols, in which diol groups -CHOH-CHOH-, containing C-C and C-O covalent bonds, are present.
[0625] For the purposes of the present invention, "depolymerizing biomass" refers to the act of breaking carbon-carbon (CC) or carbon-heteroatom (CX) covalent bonds (eg, carbon-oxygen (CO) bonds) of carbohydrate molecules contained in the biomass.
[0626] Another object of the present invention relates to a method for the degradation of biomass, comprising:
[0627] - a hydrogenolysis step of CC and CO bonds in diol groups in carbohydrate molecules contained in the biomass in the presence of a supported bimetallic catalyst having the formula CoCu / ZrO2 as defined above, said catalyst comprising copper and cobalt on a zirconium dioxide support. BRIEF DESCRIPTION OF THE DRAWINGS
[0628] The following examples and figures illustrate the present invention without limiting its scope.
[0629] Figure 1 The X-ray powder diffraction pattern of the catalyst Cu(10%)Co(5%) / ZrO2(A) prepared with ZrO2(A) carrier is shown. The specific surface area of the catalyst is about 5m 2 / g.
[0630] Figure 2 Shown is an X-ray powder diffraction pattern of a ZrO2 (A) support calcined at 600°C for 2 hours.
[0631] Figure 3 Shown with 59m 2 / g of the catalyst Cu (10%) Co (5%) / ZrO2 (B) X-ray powder diffraction pattern.
[0632] Figure 4 It shows that the product calcined at 600℃ for 2 hours has a 2 Scanning electron microscopy image of the catalyst Cu(10%)Co(5%) / ZrO2(A) with a specific surface area of 1000 nm / g.
[0633] Figure 5 Shown is a scanning electron microscopy image of a ZrO2 (A) support calcined at 600°C for 2 hours.
[0634] Figure 6 It shows that the product calcined at 600℃ for 2 hours has a 2Scanning electron microscopy image of the catalyst Cu(10%)Co(5%) / ZrO2(B) with a specific surface area of 1000 nm / g.
[0635] Figure 7 Shown are the X-ray photoelectron spectrum (spectrum A) of the catalyst Cu-Co / ZrO2(A) calcined at 600°C for 2 hours, having a composition of 10% Cu by weight and 5% Co by weight relative to the total weight of the catalyst; and the X-ray photoelectron spectrum (spectrum B) of the support ZrO2(A) used to prepare the catalyst calcined at 600°C for 2 hours.
[0636] Figure 8 Graph showing the ethylene glycol (EG) yields for experiments conducted using monometallic copper or cobalt catalysts, bimetallic copper-cobalt catalysts, and catalyst-support mixtures.
[0637] Figure 9 Graph showing the ethylene glycol (EG) yields for experiments performed using a 10% copper monometallic catalyst, a copper-cobalt bimetallic catalyst with a constant copper content of 10% and a cobalt content varying from 1% to 10%.
[0638] Figure 10 The analytical curve of temperature-programmed reduction of the prepared catalyst Cu(10%)Co(5%) / ZrO2 under dihydrogen flow (H2-TPR) in the temperature range of 100°C to 500°C.
[0639] Example
[0640] Example 1 - Materials and Methods
[0641] Two zirconium dioxide supports ZrO2 (A) and ZrO2 (B) with different specific surface areas were used to prepare the catalysts, with specific surface areas of 5 m 2 / g to 7m 2 / g of ZrO2(A) and a specific surface area of 85m 2 / g of ZrO2(B).
[0642] The specific surface area is 5m 2 / g to 7m 2 / g of zirconium dioxide support ZrO2, called ZrO2 (A), was supplied by Sterm Chemicals (15 Rue del'Atome, 67800 Bischheim) under the reference number 93-4013.
[0643] The zirconium dioxide support ZrO2 (A) provided by Sterm Chemicals comprises about 97% by weight zirconium dioxide, 1.86% by weight hafnium dioxide (HfO2), and trace amounts of silicon dioxide (SiO2) and yttrium oxide (Y2O3).
[0644] Specific surface area greater than 85m 2 / g zirconium dioxide support ZrO2, called ZrO2 (B), was provided by Thermo Fisher Scientific (formerly Alfa Aesar) with product number AA4381522.
[0645] The γ-Al 2 O 3 support was supplied by Strem Chemicals (15 Rue del'Atome, 67800 Bischheim) under the reference number 13-2525.
[0646] SiO2 supports (40 mm-63 mm) were supplied by VWR chemicals, reference number 154425P.
[0647] Cobalt nitrate (Co(NO3)2.3H2O) and copper nitrate Cu(NO3)2.3H2O were provided by Fischer.
[0648] The autoclave was supplied by Parr Instrument Company.
[0649] Example 2 - General Procedure for Preparation of Heterogeneous Catalyst Co / ZrO2
[0650] Dissolve cobalt nitrate Co(NO3)2.6H2O in a minimum volume of deionized water (5 mL to 10 mL) to form a solution. This solution containing the metal precursor is added to an appropriate amount of zirconium dioxide support ZrO2 (A) (having a 5 m 2 / g to 7m 2 / g specific surface area), and the resulting ZrO2 paste was mixed at room temperature until a homogeneous material was obtained. The material was then dried at 80°C for 16 hours and subsequently calcined at 600°C in air for 2 hours to obtain the catalyst.
[0651] Example 3 - General Procedure for Preparation of Heterogeneous Cu / ZrO2 Catalysts
[0652] Dissolve copper nitrate Cu(NO3)2.3H2O in a minimum volume of demineralized water (5 mL to 10 mL) to form a solution. This solution containing the metal precursor is added to an appropriate amount of zirconium dioxide support ZrO2 (A) (having a 5 m m diameter as measured by BET). 2 / g to 7m 2 / g specific surface area), and the resulting ZrO2 paste was mixed at room temperature until a homogeneous material was obtained. The material was then dried at 80°C for 16 hours and subsequently calcined at 600°C in air for 2 hours to obtain the catalyst.
[0653] Example 4 - General Procedure for Preparation of Heterogeneous Catalyst Cu-Co / ZrO2 (A)
[0654] Dissolve cobalt nitrate Co(NO3)2.6H2O and copper nitrate Cu(NO3)2.3H2O in a minimum volume of demineralized water (5 mL to 10 mL) to form a solution. Add this solution containing the metal precursors to an appropriate amount of 5 mL of water. 2 / g to 7m 2 / g of surface area of support ZrO2 (A) and mixed at room temperature until a homogeneous material was obtained. The material was then dried at 80°C for 16 h and subsequently calcined at 600°C in air for 2 hours to obtain the catalyst.
[0655] Example 5 - Preparation of heterogeneous monometallic and bimetallic catalysts Co / ZrO2, Cu / ZrO2, Cu-Co / ZrO2, wherein the zirconium dioxide has 5m 2 / g to 7m 2 Specific surface area / g
[0656] Table 1 below reports the preparation conditions of the catalysts Co / ZrO2, Cu / ZrO2 and Cu-Co / ZrO2 prepared according to Example 2, Example 3 and Example 4 using the support.
[0657] Table 1: Specific surface area of 5m 2 / g to 7m 2 / g ZrO2 (A) catalysts Co / ZrO2, Cu / ZrO2 and Cu-Co / ZrO2
[0658]
[0659] Example 6 - General Procedure for Preparation of Heterogeneous Cu-Co / Support Catalysts
[0660] Dissolve cobalt nitrate Co(NO3)2.6H2O and copper nitrate Cu(NO3)2.3H2O in a minimum volume of demineralized water (5 mL to 10 mL) to form a solution. Add this solution containing the metal precursors to an appropriate amount of support (with a mass greater than 85 m 2 / g specific surface area of ZrO2 (B), SiO2, CeO2 or γ-Al2O3) and mixed at room temperature until a homogeneous material was obtained. The material was then dried at 80°C for 16 hours and then calcined at 600°C in air for 2 hours to obtain the catalyst.
[0661] Table 2 below reports the preparation conditions of the catalyst Cu—Co / support prepared according to Example 6.
[0662] Table 2: Cu-Co / support of catalysts prepared with various supports
[0663]
[0664] Example 7 - General Procedure for Heterogeneous Catalysis of the Hydrogenation of Dialkyl Oxalates in a 450 mL Reactor
[0665] Based on copper (4mmol Cu) or based on copper (4mmol Cu) and cobalt or based on cobalt (4mmol Co) heterogeneous catalyst, diethyl oxalate (20mmol) and ethanol (50mL) as solvent are introduced in the 450mL Parr autoclave equipped with magnetic stirrer.The reactor is sealed, and the reaction mixture is purged three times with nitrogen (5bar), and purged twice with hydrogen (5bar).
[0666] The autoclave was then pressurized with 50 bar of hydrogen.The reaction medium was then stirred at 200° C. for 16 hours or at 220° C. for 8 hours.
[0667] When the reaction was complete, the autoclave was returned to room temperature, decompressed, and purged with nitrogen (5 bar) three times.
[0668] The finally obtained mixture was diluted in ethanol or methanol, and then an internal standard (mesitylene) was added to calculate the yield by using GC-MS.
[0669] Example 8 - Experiments using catalysts Cu / ZrO2(A), Co / ZrO2(A) and CoCu / ZrO2(A)
[0670] Table 3 reports the conditions of the hydrogenation tests on the catalysts Cu / ZrO2(A), Co / ZrO2(A) or CoCu / ZrO2(A) prepared according to Example 5, as well as the yield (Yld) and selectivity (selec). The hydrogenation yield and selectivity were calculated by GC-MS, using mesitylene as an internal standard. Table 3: Conditions of the hydrogenation tests on the catalysts Cu / ZrO2(A), Co / ZrO2(A) or CoCu / ZrO2(A) and the results obtained
[0671]
[0672]
[0673]
[0674] Example 9 - Tests on various substrates prepared according to Example 6 using the catalyst CoCu
[0675] Table 4 reports the conditions, yields (Yld) and selectivities (selec) of hydrogenation experiments for various substrates using the CoCu catalyst prepared according to Example 6. The hydrogenation efficiency and selectivity were calculated using GC-MS, with mesitylene used as an internal standard.
[0676] Table 4: Conditions and results of hydrogenation tests with CoCu catalysts on various supports
[0677]
[0678] Example 10 - General Procedure for Heterogeneous Catalysis of the Hydrogenation of Diethyl Oxalate in a 1 Liter Reactor
[0679] A copper (40 mmol Cu)-based heterogeneous catalyst, diethyl oxalate (200 mmol) and ethanol (400 mL) as a solvent were introduced into a 1 liter Parr autoclave equipped with a magnetic stirrer. The reactor was sealed and the reaction mixture was purged three times with nitrogen (5 bar) and twice with hydrogen (5 bar).
[0680] The autoclave is then pressurized with 50 bar of hydrogen.The reaction medium is then heated to 200° C. for 16 hours or to 220° C. for 8 hours.
[0681] When the reaction was complete, the autoclave was returned to room temperature, decompressed, and purged with nitrogen (5 bar) three times.
[0682] Ethylene glycol was recovered after purification by vacuum distillation at 120°C / 5 mbar.
[0683] Example 11. Tests carried out in a 1-liter reactor with the catalyst CoCu / ZrO2(A) Table 5 reports the conditions and the yield (Yld) of the hydrogenation test of oxalate, diethyl oxalate (DEO), carried out in a 1-liter reactor with the catalyst CoCu / ZrO2(A) according to Example 11. The yield of ethylene glycol formed at the end of the hydrogenation step was calculated using GC-MS, using mesitylene as an internal standard.
[0684] Table 5: Experimental conditions and results obtained for hydrogenation using the catalyst CoCu / ZrO2 (A) in a 1-liter reactor.
[0685]
[0686] Example 12 - General Procedure for Catalyst Recycling After Hydrogenation of Dialkyl Oxalates
[0687] After the dialkyl oxalate hydrogenation reaction, the Co(5%)Cu(10%) / ZrO2(A) catalyst was separated from the liquid reaction medium by filtration. The catalyst was then washed three times with 25 mL of ethanol and centrifuged. The material was then dried at 80°C for 4 hours and subsequently reused in the dialkyl oxalate hydrogenation reaction under the same conditions as Reaction 7 in Table 3.
[0688] Example 13 - Catalyst Recycling Test after Hydrogenation of Dialkyl Oxalate
[0689] Table 6 below reports the recycling results according to Example 12, respectively.
[0690] Table 6: Productivity and selectivity of recycled catalyst
[0691]
[0692]
[0693] Example 14 - BET Analysis of Catalyst Cu-Co / ZrO2
[0694] Table 7 below shows the average specific surface area of the catalysts Cu(10%)-Co(5%) / ZrO2 prepared using various zirconium dioxide supports after calcination at 600°C for 2 hours as determined by BET analysis.
[0695] Table 7: BET average specific surface area of Cu-Co / ZrO2 catalyst after calcination
[0696] Compound <![CDATA[Average specific surface area (m 2 / g)]]> <![CDATA[ZrO2(A)]]> 6.11 <![CDATA[Co(5%)Cu(10%)ZrO2(A)]]> 5.44 <![CDATA[Co(5%)Cu(10%)ZrO2(B)]]> 59.09
[0697] Example 15: Structural Analysis
[0698] A. Phase Analysis
[0699] The X-ray powder diffractograms of the materials (catalysts or supports) were carried out using a MINIFLEX II diffractometer from Rigaku, which emits X-ray radiation (wavelength Kα) via a tube and a copper source. ).
[0700] Figure 1 The obtained calcined at 600 ° C for 2 hours has a 5.4 m 2 RX diffraction pattern of catalyst Co(5%)Cu(10%) / ZrO2(A) with a specific surface area of 1.577 W / g.
[0701] Figure 2 The obtained calcined at 600 ° C for 2 hours has a 6.1m 2 RX diffraction pattern of the carrier ZrO2 (A) used with a specific surface area of 1.574 nm / g.
[0702] Figure 3 The obtained calcined at 600 ° C for 2 hours has a 59m 2 RX diffraction pattern of the catalyst Co(5%)Cu(10%) / ZrO2(B) with a specific surface area of 1.577 W / g.
[0703] The utilization results of the different diffraction patterns obtained are shown in Tables 8 to 10 below:
[0704] - Catalyst Co(5%)Cu(10%) / ZrO2(A) in Table 8,
[0705] - support ZrO2 (A) in Table 9,
[0706] - Catalyst Co(5%)Cu(10%) / ZrO2(B) in Table 10.
[0707] Table 8: Phase analysis in catalyst Co(5%)Cu(10%) / ZrO2(A)
[0708]
[0709] Table 9: Phase analysis in calcined support ZrO2 (A)
[0710]
[0711]
[0712] Table 10: Phase analysis in catalyst Co(5%)Cu(10%) / ZrO2(B)
[0713]
[0714] The diffraction pattern showed the presence of a crystalline phase.
[0715] XRD analysis indicated that the crystalline phase of baddeleyite (ZrO2) existed in the catalytic samples ZrO2(A), Co(5%)Cu(10%) / ZrO2(A) and Co(5%)Cu(10%) / ZrO2(B).
[0716] The diffraction pattern of the sample Co(5%)Cu(10%) / ZrO2(A) reveals the presence of two additional crystalline phases of copper(I) oxide Cu2O and copper(II) oxide CuO with weak signals.
[0717] The diffraction pattern of the sample Co(5%)Cu(10%) / ZrO2(B) reveals the presence of two additional crystalline phases of cobalt oxides CoO and Co3O4 with low intensity.
[0718] B. Crystallinity-Microstructure: Grain Size Analysis
[0719] Grain size
[0720] The crystallinity of a material is characterized by its grain size.
[0721] In order to compare different ZrO2 supports of the catalysts, a qualitative evaluation of the crystallite size was performed.
[0722] The grain size is evaluated according to the following Scherrer formula:
[0723]
[0724] The peak width at half height was estimated using ImageJ processing software (developed by the National Institutes of Health).
[0725] The grain sizes calculated from the diffraction patterns of the catalysts Co(5%)Cu(10%) / ZrO2(A) and Co(5%)Cu(10%) / ZrO2(B) are shown in Table 11 below:
[0726] Table 11: Grain size
[0727]
[0728] The carrier ZrO2(B) used to prepare Co(5%)Cu(10%) / ZrO2(B) was a commercial ZrO2 oxide powder from Alfa Aesar with a pore volume of 0.27cc / g and a specific surface area of more than 85m 2 / g(BET).
[0729] Small size values (especially less than 10 nanometers) indicate that the structure has a low degree of crystallinity. In fact, the smaller the grains, the broader the diffraction peaks. This effect becomes significant for grains with a diameter of less than 1 μm.
[0730] The results show that the catalyst prepared using the ZrO2 (A) support from Sterm according to the present invention and the catalyst prepared using the ZrO2 (B) support from Alfa Aesar according to the present invention had grain sizes of 21 nm and 9 nm, respectively. Therefore, catalysts Cat A and Cat B differ in the microstructure of the ZrO2 support.
[0731] Apart from the features relating to the specific surface area, these results show that the supports of the catalysts Cat A and Cat B according to the invention differ in their microstructure.
[0732] Example 16: Morphological Analysis
[0733] Figures 4 to 6The SEM images in were taken using a Zeiss SEM-FEG scanning microscope with pressure control, which enables the observation of materials with low or no electrical conductivity without any specific preparation.
[0734] The samples were stabilized on carbon adhesive paper to enable SEM observation. It should therefore be noted that the content of elemental carbon may be related to the use of the latter. The results of SEM observation and EDX analysis are summarized below.
[0735] Catalyst Co(5%)Cu(10%) / ZrO2(A)
[0736] Figure 4 Observation of the SEM images in [ 1 ] revealed the presence of a cluster of particles with a rounded morphology. These particles are primarily composed of zirconium (Zr), copper (Cu), oxygen (O), carbon (C), and cobalt (Co), with small amounts of hafnium (Hf), rhenium (Re), and trace amounts of silicon (Si). EDX spectroscopy was used to quantify the distribution of these particles. The results, expressed as mass percentages, are shown in Table 12.
[0737] Table 12: Chemical composition of catalyst Co(5%)Cu(10%) / ZrO2(A)
[0738] element Quantification using EDX spectroscopy (in wt%) C 11.01 O 17.07 Si 0.29 Co 6.55 Cu 19.43 Zr 42.91 Hf 1.34 Re 1.40 total 100.00
[0739] Calcinated ZrO2(A) support
[0740] right Figure 5 Observation of the SEM images in the
[15] reveals the presence of multiple particle populations (rounded, spherical, and angular morphologies). The predominant population has a rounded morphology, similar to that of the Co(5%)Cu(10%) / ZrO2 sample. These particles are primarily composed of zirconium (Zr), oxygen (O), and carbon (C), with trace amounts of rhenium (Re), hafnium (Hf), and silicon (Si).
[0741] The minor group has a spherical morphology and is composed mainly of zirconium (Zr), oxygen (O) and carbon (C), with small amounts of hafnium (Hf) and rhenium (Re) and trace amounts of silicon (Si).
[0742] EDX spectroscopy was used to quantify two regions of the particles of the support calcined at 600° C. for 2 hours. The results are shown in Table 13 as weight percent.
[0743] Table 13: Chemical composition of ZrO2(A) support
[0744]
[0745] Catalyst Co(5%)Cu(10%) / ZrO2(B)
[0746] right Figure 6 Observation of the SEM images in the 20 ...
[0747] The areas of these particles were quantified by EDX spectroscopy. The results expressed as weight percent are shown in Table 14.
[0748] Table 14: Chemical composition of catalyst Co(5%)Cu(10%) / ZrO2(B)
[0749] element Quantification by EDX spectroscopy (in wt%) C 3.99 O 17.817 Co 11.49 Cu 27.71 Zr 39.00 total 100.00
[0750] Example 17: Surface analysis by XPS
[0751] The analyses were performed using a PHIQUANTES photoemission spectrometer equipped with a monochromatic X-ray source (aluminum Kα line), a chromium X-ray source for hard XPS, a charge neutralization system for electrically insulating samples, and a hemispherical electron analyzer.
[0752] XPS analysis was performed on the catalyst Co(5%)Cu(10%) / ZrO2(A) calcined at 600°C for 2 hours and the ZrO2(A) support sample calcined at 600°C for 2 hours.
[0753] The XPS spectrum is shown in Figure 7 middle.
[0754] The quantification of the outermost surface of the two samples is shown in Table 15 below, expressed as mass percentage:
[0755] Table 15: Chemical composition by XPS
[0756] atom <![CDATA[Co(5%)Cu(10%)ZrO2(%)]]> <![CDATA[ZrO2(%)]]> Oxygen (O) 34.96 39.74 Zirconium (Zr) 44.53 54.11 Cobalt (Co) 5.71 / Copper (Cu) 11.13 /
[0757] Both samples have low carbon content, mainly from atmospheric pollution.
[0758] Co (5 wt %) Cu (10 wt %) ZrO 2 as sample 22 consists of zirconium (Zr), oxygen (O), copper (Cu), cobalt (Co), and trace amounts of silicon (Si) and sodium (Na).
[0759] Sample ZrO2 consists of zirconium (Zr) and oxygen (O) with trace amounts of silicon (Si) and sodium (Na).
[0760] Determination of the chemical environment
[0761] The results of Gaussian deconvolution of the spectra are shown in Table 16 below:
[0762] Table 16: Results of XPS analysis
[0763]
[0764] C1s spectrum:
[0765] For all samples, deconvolution of the C1s carbon spectra showed two components:
[0766] The main component at 285.0 eV is characterized by C—C and C—H bonds. These bonds originate from air contamination.
[0767] The component at -288.40 eV is characterized by CO and C=O bonds. These bonds also represent surface contamination.
[0768] O1s spectrum:
[0769] For all samples, deconvolution of the O1s oxygen spectrum showed two components:
[0770] - The major component at 531.0 eV is typically characterized as an oxide.
[0771] The component at -531.2 eV is characterized by transition metal oxides.
[0772] Si2p spectrum:
[0773] For all samples, deconvolution of the Si2p silicon spectrum revealed two components:
[0774] - The main component at 103.3 eV is characterized by silicon oxide SiOx.
[0775] The component at -102.0 eV is characterized by silicon oxide SiO2.
[0776] It should be noted that the characteristic components of cobalt (II) oxide CoO are at the same energy as the components corresponding to SiOx.
[0777] Na1s spectrum:
[0778] For all samples, deconvolution of the Na1s spectra revealed a single component characteristic of air pollution.
[0779] Cu2p3 / 2 spectrum:
[0780] For the sample Co(5wt%)Cu(10wt%)ZrO2, the deconvolution of the copper 2p3 / 2 spectrum has two components:
[0781] - The main component at 934.0 eV is characterized by copper (II) oxide CuO.
[0782] The two strong satellite components at 943.5 eV and 963.5 eV are characterized by Cu 2+ ions and is therefore characterized as copper (II) oxide CuO.
[0783] - The component at 932.6 eV is characterized by metallic copper or copper (I) oxide Cu2O.
[0784] Co2p3 / 2 spectrum:
[0785] For the sample Co(5%)Cu(10%)ZrO2, the spectrum of cobalt 2p3 / 2 presents characteristic components of cobalt(III) oxide Co2O3 and cobalt(II) oxide CoO as well as cobalt(II) hydroxide Co(OH)2.
[0786] High-resolution XPS spectrum of zirconium 3d5 / 2
[0787] XPS analysis revealed the presence of primarily zirconium oxide (ZrO2), trace amounts of silicon oxides (SiO2 and SiOx) and surface contamination (carbon and sodium) for all samples.
[0788] Sample Co(5%)Cu(10%) / ZrO2 shows the additional presence of copper in two oxidized forms: CuO and Cu2O. XPS analysis also reveals that for this sample, cobalt is present in the form of cobalt hydroxide Co(OH)2 or cobalt(II) oxide CoO or cobalt(III) oxide Co2O3.
[0789] Example 18 - Continuous Flow Hydrogenation Procedure
[0790] The 0.05M to 0.5M diethyl oxalate solution in ethanol is pumped into the reactor at a rate of 0.3mL / min to 3mL / min. Then, the pressure of the system is set between 30bar and 100bar using a back pressure regulator, and the reactor is subsequently heated to between 150°C and 220°C. The reactor is composed of a stainless steel tube, and the catalyst (between 150mg and 700mg) for reaction is positioned therein. Finally, the hydrogen produced in situ by a valve is introduced from the outside or injected into the system with the desired flow rate between 20mLN / min and 100mLN / min. Optionally, before introducing a reagent, the catalyst is first contacted with a stream of hydrogen. When the system is stable, before being analyzed by GC-MS, the product is collected in a bottle at the reactor outlet.
[0791] Example 19 - Procedure for Degradation of Ethylene Glycol by Reduction in the Presence of CuCo / ZrO2 Catalysts
[0792] A copper (4 mmol Cu) and cobalt-based heterogeneous catalyst, ethylene glycol (10 mmol), a base (potassium tert-butoxide (KOtBu)) and tetrahydrofuran (THF, 75 mL) as solvent were introduced into a 450 mL Parr autoclave equipped with a magnetic stirrer. The reactor was sealed and the reaction mixture was purged three times with nitrogen (5 bar) and twice with hydrogen (5 bar).
[0793] The autoclave is then pressurized with 60 bar of hydrogen.The reaction medium is then stirred at 180° C. to 200° C. for 15 hours.
[0794] When the reaction was complete, the autoclave was returned to room temperature, decompressed, and purged with nitrogen (5 bar) three times.
[0795] The final mixture obtained was diluted and an internal standard (mesitylene) was added to calculate the conversion of ethylene glycol using GC-MS.
[0796] The equilibrium of the degradation reaction of ethylene glycol by hydrogenation in the presence of the CuCo / ZrO2 catalyst is as follows:
[0797]
[0798] Example 20 - Tests with Catalyst CoCu / ZrO2 (A)
[0799] Table 17 shows the conditions for the hydrogenation degradation test of ethylene glycol in the presence of the catalyst CoCu / ZrO2(A) prepared according to Example 5. The ethylene glycol conversion was calculated using GC-MS, with mesitylene used as an internal standard.
[0800] Table 17: Experimental conditions and results obtained for the hydrogenation of ethylene glycol in the presence of the catalyst CoCu / ZrO2 (A)
[0801]
[0802]
[0803] Example 21: Synergistic and Promoter Effects of Cobalt on Zirconium Dioxide-Supported Copper-Based Catalysts in the Hydrogenation of Oxalates for the Preparation of Ethylene Glycol
[0804] Tests using mixtures
[0805] Experiment CUCOMIX01 was prepared according to the conditions of Experiments A-2 and A-1 in Example 7, using an equimolar mixture of two monometallic catalysts Co(5%) / ZrO2 and Cu(10%) / ZrO2 as the catalytic material, and the hydrogenation reaction time was 10 hours instead of 16 hours.
[0806] Test CUCMIX02 was prepared according to the conditions of Test A-7 in Example 7, with the addition of support material (ZrO2) and a reaction time of 10 hours instead of 16 hours.
[0807] Table 18 below shows the results of substrate conversion (oxalate), ethylene glycol yield and selectivity for ethylene glycol production from oxalate hydrogenation experiments under similar conditions (temperature, pressure, time) in the presence of:
[0808] - monometallic cobalt or nickel supported catalysts (Test A-1, Test A-2 and Test A-3),
[0809] or
[0810] - a mixture of two monometallic catalysts (CUCOMIX01 test), or
[0811] - a mixture of a bimetallic catalyst and an equal weight of a support (zirconium dioxide), or
[0812] - Bimetallic catalysts based on copper and cobalt at a constant copper content, ie a copper content of 10% by weight, based on the total weight of the catalyst (Tests A-6 and A-7).
[0813] Table 18: Results of oxalate conversion, EG yield and EG selectivity obtained in oxalate hydrogenation experiments in the presence of copper and / or cobalt catalysts on zirconium dioxide supports
[0814]
[0815] For the hydrogenation of oxalate to ethylene glycol (EG), the following table shows the reaction conditions: Figure 8 The results of the test series in show that:
[0816] 1) The monometallic cobalt catalyst supported on zirconium dioxide is inactive. Catalysts with two cobalt contents, Co(5%)ZrO2 and Co(10%)ZrO2, were tested and
[0817] The same results were obtained: cobalt supported on zirconium dioxide showed no catalytic activity after 16 hours of reaction.
[0818] 2) The monometallic copper catalyst supported on zirconium dioxide was active, but the yield of ethylene glycol was still low (12%) even after 16 h of reaction with the catalyst Cu(10%) / ZrO2.
[0819] 3) The bimetallic catalysts based on copper and cobalt at 10% on zirconium dioxide (i.e., Co(5%)Cu(10%) / ZrO2 and Co(10%)Cu(10%) / ZrO2) are more active than the monometallic copper catalyst Cu(10%) / ZrO2. This alone demonstrates the promoter effect in the presence of cobalt, whereas in the absence of copper, cobalt appears inactive at these percentages (5% and 10%).
[0820] 4) The activity of the mixture of monometallic catalysts Co(5%) / ZrO2+Cu(10%) / ZrO2 was lower than that of the bimetallic catalyst Co(5%)Cu(10%)ZrO2, demonstrating the synergistic effect between cobalt and copper, which may be due to the promoting effect of cobalt, which makes it possible to tune the catalytic activity of copper supported on zirconia.
[0821] Example 22: Effect of Cobalt Content on the Hydrogenation of Oxalate Esters of Ethylene Glycol over Bimetallic Catalysts Based on Copper and Cobalt on Zirconium Dioxide
[0822] Table 19 below shows the results of substrate conversion (oxalate), ethylene glycol yield and selectivity for ethylene glycol production from oxalate hydrogenation tests under similar conditions (temperature, pressure, time) in the presence of a supported catalyst based on copper (copper at a constant ratio, i.e. a copper content of 10% based on the total weight of the catalyst), in the absence of cobalt and in the presence of a cobalt content varying from 1% to 10% based on the total weight of the catalyst.
[0823] Table 19: Results of oxalate conversion, EG yield and EG selectivity obtained in oxalate hydrogenation tests in the presence of catalysts based on a constant copper content of 10% in the absence of cobalt and in the presence of cobalt in an amount ranging from 1% to 10% on a zirconium dioxide support
[0824]
[0825] For the hydrogenation of oxalate to ethylene glycol (EG), the following table shows the reaction conditions: Figure 9 The results of the test series in show that:
[0826] 5) Cobalt as a reaction aid improves the catalytic activity of the catalyst CoCu / ZrO2, showing a peak when the percentage of cobalt is 5%, and when the percentage of cobalt is 10%
[0827] activity decreases when the reaction temperature is lower than that of the active ingredient, which is typical behavior expected from an adjuvant effect.
[0828] The conclusion is that cobalt plays a promoter function in the CuCo / ZrO2 catalyst.
[0829] Example 23: Analysis of CuCo / ZrO2 catalyst by temperature-programmed reduction
[0830] Materials and methods
[0831] Temperature programmed reduction (PTR) or (TRP) analysis is used to characterize solid materials, including metal oxides (oxide type, oxide mixture, dispersion on a support). This analytical technique, performed under a reducing atmosphere, is known to the skilled person for characterizing heterogeneous catalysts.
[0832] It consists of determining the amount of hydrogen consumed as a function of temperature. It enables determination of the temperature at which the reduction from the oxidized form to the metallic form occurs, and of the possible nature of the metal oxides and the ratios between the metal oxides present.
[0833] The measurements were performed by temperature-programmed reduction in hydrogen (H2-TPR) using a Micromeritics AutochemII 2920 analyzer.
[0834] In a typical experiment, a 50 mg sample was pretreated at 200°C (heating rate = 10°C / min) for 30 min under a helium (He) flow (30 mL / min). The sample was then cooled to 30°C, maintaining the He flow. Reduction analysis was performed from 30°C to 900°C (heating rate = 5°C / min) under a 5 vol% H2 in argon flow (30 mL / min). The final temperature (900°C) was maintained for 30 minutes.
[0835] exist Figure 10 Figure 2 shows the H2-RTP analysis curve of the catalyst Co(5%)Cu(10%) / ZrO2 in the temperature range from 100°C to 500°C. It shows that the low-temperature reduction peak has two maxima at 155°C and 174°C, which can be corresponding to the continuous reduction of CuO to Cu2O and Cu2O to Cu, respectively. In addition, the high-temperature reduction peak centered at 221°C may be related to the reduction of Co3O4 to CoO and the further reduction of Co.
Claims
1. A method for preparing ethylene glycol from an oxalate compound by hydrogenating the oxalate compound with hydrogen (H2) to obtain ethylene glycol, wherein the catalyst comprises copper and cobalt on a zirconium dioxide support.
2. The use according to claim 1, wherein The catalyst had a surface area of 1 m 2 / g to 250m 2 / g, especially 1m 2 / g to 50m 2 / g, preferably 1m 2 / g to 10m 2 / g, especially about 5m 2 / g, Optionally, the catalyst includes a crystalline phase, which is monoclinic crystallized by X-ray diffraction analysis, and in particular, the crystalline phase accounts for 50% to 90% of the total weight of the catalyst. Preferably, the crystalline phase is baddeleyite, and its grain size is preferably 15nm to 100nm.
3. The use according to any one of claims 1 to 2, wherein The hydrogenation reaction of the oxalate compound to obtain ethylene glycol by hydrogen is selective, and the selectivity is greater than 70%, preferably greater than 90%, more preferably greater than or equal to 95%, And / or wherein the hydrogenation reaction of the oxalate compound with hydrogen to obtain ethylene glycol has a yield greater than 70%, preferably greater than 80%.
4. A method for preparing ethylene glycol, comprising: o A hydrogenation step of an oxalate compound to ethylene glycol by hydrogen in the presence of a supported bimetallic catalyst having the formula CoCu / ZrO2 comprising copper and cobalt on a zirconium dioxide support.
5. The method for preparing ethylene glycol according to claim 4, wherein The hydrogenation step includes o contacting the following to obtain a reaction medium that can be pressurized: - the oxalate compound, -dihydrogen, - said supported catalyst having the formula CoCu / ZrO2, said catalyst comprising cobalt and copper on a zirconium dioxide support, - optionally a solvent, o the reaction medium may be heated, to obtain ethylene glycol.
6. The method for preparing ethylene glycol according to any one of claims 4 to 5, wherein: The oxalate compound has the following formula 1: Among them, R a express: C1 to C 20 a straight-chain or branched alkyl group, C3 to C 10 cycloalkyl groups, C3 to C 20 an aryl or heteroaryl group, C5 to C 20 an alkyl-aryl or alkyl-heteroaryl group, In particular, the oxalate compound is selected from dimethyl oxalate, diethyl oxalate, diphenyl oxalate, dibenzyl oxalate, isopropyl oxalate and di-tert-butyl oxalate.
7. The method for preparing ethylene glycol according to any one of claims 4 to 6, in, The catalyst comprises bimetallic elements copper and cobalt in an amount of 0.5% to 25% by weight based on the total weight of the catalyst. and wherein the weight ratio of cobalt to copper varies from 1:1 to 1:5, In particular, the mass composition of cobalt and copper of the catalyst is selected from: -Co(2%)Cu(10%), -Co(5%)Cu(10%), -Co(5%)Cu(5%), - and Co(10%)Cu(10%), Preferably, Co(2%)Cu(10%) and Co(5%)Cu(10%), More preferably, Co(5%)Cu(10%).
8. The method for preparing ethylene glycol according to any one of claims 4 to 7, in, The zirconium dioxide support of the catalyst CoCu / ZrO2 comprises baddeleyite in an amount of 50% to 90% based on the total weight of the catalyst.
9. The method for preparing ethylene glycol according to any one of claims 4 to 8, in, using the hydrogen at a pressure of 2 MPa to 10 MPa, in particular 6 MPa, wherein the reaction medium is heated to a temperature of 100° C. to 250° C., in particular 180° C. to 220° C., optionally wherein the reaction medium is heated for 5 hours to 24 hours, in particular 8 hours or 16 hours, wherein, during the step of heating the reaction medium, the supported bimetallic catalyst is activated, and the activated catalyst comprises: 80% to 100%, in particular 95% to 100%, preferably 100%, of metallic copper atoms Cu(0) in a zero oxidation state, and - 80% to 100% of the cobalt atoms are in a degree of oxidation greater than zero.
10. A supported bimetallic catalyst having the formula CoCu / ZrO2, said catalyst comprising copper and cobalt on a zirconium dioxide support, in, The catalyst had a surface area of 1 m 2 / g to 75m 2 / g, preferably, 1m 2 / g to 50m 2 / g. The catalyst according to claim 10 , wherein The catalyst had a surface area of 1 m 2 / g to 10m 2 / g, especially about 5m 2 / g.
12. The catalyst according to any one of claims 10 to 11, wherein The zirconium dioxide carrier includes a crystalline phase, and X-ray diffraction analysis shows that the phase is monoclinic.
13. The catalyst according to claim 12, wherein The crystalline phase accounts for 50% to 90% of the total weight of the catalyst.
14. The catalyst according to any one of claims 12 to 13, wherein The crystalline phase is baddeleyite.
15. The catalyst according to any one of claims 10 to 14, wherein The catalyst includes a crystalline phase, and according to X-ray diffraction analysis, the crystalline phase includes a crystallite size of 15 nm to 100 nm.
16. The catalyst according to any one of claims 10 to 15, wherein The catalyst includes bimetallic elements copper and cobalt in a total content of 0.5% to 25% based on the total weight of the catalyst.
17. The catalyst according to any one of claims 10 to 16, wherein The weight ratio of cobalt to copper varied from 1:1 to 1:
5.
18. The catalyst according to any one of claims 10 to 17, wherein The mass composition of cobalt and copper of the catalyst is selected from: -Co(2%)Cu(10%), -Co(5%)Cu(10%), -Co(5%)Cu(5%), - and Co(10%)Cu(10%), Preferably, Co(2%)Cu(10%) and Co(5%)Cu(10%), More preferably, Co(5%)Cu(10%).
19. The catalyst according to any one of claims 10 to 18, wherein The catalyst has a molar amount of more than 50% of elemental copper in oxidation degree (II) and / or elemental cobalt in oxidation degree (II).
20. The catalyst according to any one of claims 10 to 19, wherein The catalyst is in the form of a population of micronized particles ranging from 1 μm to 500 μm, preferably in the form of a population of particles with a rounded morphology.
21. The catalyst according to any one of claims 10 to 20, wherein The catalyst is analyzed by performing temperature programmed reduction (TPR) in a dihydrogen reducing atmosphere at a temperature range of 30° C. to 900° C., wherein the reduction temperature of metallic copper with an oxidation degree (0) is in the range of 150° C. to 250° C., In particular at a temperature at least 10° C. higher than said reduction temperature of metallic copper analyzed by TPR, 80% to 100%, preferably 100%, of the copper atoms are in metallic form, 80% to 100%, preferably 100%, of the cobalt atoms are in oxidized form.
22. The catalyst according to any one of claims 10 to 21, in, In a reducing atmosphere including hydrogen, at a pressure of 2 MPa to 10 MPa and a temperature of 150° C. to 250° C., particularly 180° C. to 220° C., the catalyst comprises: 80% to 100%, in particular 95% to 100%, preferably 100%, of metallic copper atoms Cu(0), and - 80% to 100% of the cobalt atoms are in a degree of oxidation greater than zero.
23. A method for preparing the catalyst CoCu / ZrO2 according to any one of claims 10 to 22, the method comprising: Step A, impregnating a zirconium dioxide support in powder form with a cobalt salt and a copper salt dissolved in an aqueous solution free of additives and surfactants, wherein the aqueous solution is 5 mL to 10 mL by volume of water and the ratio of the solution mass to the support mass is 0.6 to 1.0; To obtain the catalyst CoCu / ZrO2 in the form of a homogeneous mixture, The carrier has 1m 2 / g to 75m 2 / g, preferably 1m 2 / g to 50m 2 / g, preferably 1m 2 / g to 10m 2 / g, especially about 5m 2 / g surface area, and comprising a crystalline phase, which is monoclinic crystallized by X-ray diffraction analysis, step B, drying the homogeneous material at a temperature of 60° C. to 100° C. for a period of 10 to 24 hours to obtain the catalyst CoCu / ZrO2 in the form of a dry homogeneous mixture, • An activation step C comprising calcining said dried homogeneous mixture at a temperature ranging from 200° C. to 1000° C. for a period ranging from 1 hour to 15 hours under air to obtain said catalyst.
24. A supported bimetallic catalyst having the formula CoCu / ZrO2, said catalyst comprising copper and cobalt on a zirconium dioxide support, said catalyst being obtainable by the process of claim 23.
25. The catalyst according to claim 24, wherein The catalyst is analyzed by performing temperature programmed reduction (TPR) in a dihydrogen reducing atmosphere at a temperature range of 30° C. to 900° C., wherein the reduction temperature of metallic copper with an oxidation degree (0) is in the range of 150° C. to 250° C., In particular, at a temperature at least 10° C. higher than the reduction temperature of said metallic copper as analyzed by TPR, 80% to 100%, preferably 100%, of the copper atoms are in metallic form, 80% to 100%, preferably 100%, of the cobalt atoms are in oxidized form.
26. The catalyst according to any one of claims 24 or 25, wherein Under a reducing atmosphere including hydrogen, at a pressure of 2 MPa to 10 MPa and a temperature of 150° C. to 250° C., particularly 180° C. to 220° C., the catalyst comprises: 80% to 100%, in particular 95% to 100%, preferably 100%, of metallic copper atoms Cu(0), and - 80% to 100% of the cobalt atoms are in a degree of oxidation greater than zero.
27. An activated supported bimetallic catalyst having the formula CuCo / ZrO2, said catalyst comprising copper and cobalt on the surface of a zirconium dioxide support, wherein 80% to 100%, in particular 95% to 100%, preferably 100%, of the copper atoms are in the zero oxidation state Cu(0), and 80% to 100%, in particular 95% to 100%, preferably 100%, of the cobalt atoms are in a degree of oxidation greater than zero.
28. The method according to any one of claims 4 to 9, wherein The catalyst is the catalyst according to any one of claims 10-22 and 24-27.
29. Use of the catalyst CoCu / ZrO2 according to any one of claims 10 to 22 and 24 to 27 for the hydrogenolysis of ethylene glycol.
30. Use of the catalyst CoCu / ZrO2 according to any one of claims 10 to 22 and 24 to 27 for depolymerizing biomass by hydrogenolysis of the glycol groups present in the compounds constituting said biomass.